Toner set for developing electrostatic images, electrophotographic image forming method and electrophotographic image forming apparatus

A dual-cyan toner set using silicon and copper phthalocyanine compounds addresses the challenge of achieving expanded color gamut and smooth gloss in toner images, enhancing image quality and stability.

JP7615567B2Active Publication Date: 2025-01-17KONICA MINOLTA INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020140382
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-21
Publication Date
2025-01-17
Estimated Expiration
2040-08-21

AI Technical Summary

Technical Problem

Existing toners face challenges in achieving a good image quality with expanded color gamut in low brightness areas and smooth gloss in medium brightness areas, often resulting in unstable toner chargeability and unsatisfactory image formation due to increased colorant content.

Method used

A toner set comprising at least two types of cyan toners, one containing a silicon phthalocyanine compound and the other a copper phthalocyanine compound, with a hue angle difference of 10° or more, is used to develop electrostatic images, enhancing color reproducibility and gloss stability.

Benefits of technology

The toner set achieves expanded color gamut in low brightness areas and smooth gloss in medium brightness areas, providing high chroma cyan images with improved chargeability and gloss stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615567000012
    Figure 0007615567000012
  • Figure 0007615567000013
    Figure 0007615567000013
  • Figure 0007615567000001
    Figure 0007615567000001
Patent Text Reader

Abstract

To provide a toner set for electrostatic charge image development, an electrophotographic image forming method, and an electrophotographic image forming apparatus with which a satisfactory image can be obtained in terms of the expansion of the color gamut of a low brightness part and smoothness of the glossiness of a medium brightness part.SOLUTION: A toner set for electrostatic charge image development consists of at least two types of cyan toner. The first cyan toner contains a silicon phthalocyanine compound having a structure represented by the general formula (I), and the second cyan toner contains a copper phthalocyanine compound.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner set for developing electrostatic images, an electrophotographic image forming method and an electrophotographic image forming apparatus. More specifically, the present invention relates to a toner set for developing electrostatic images that can provide a good image with an expanded color gamut in low lightness areas and smooth gloss in medium lightness areas. [Background technology]

[0002] In the field of print-on-demand printing, which has become increasingly popular in recent years due to the convenience and speed of data processing, there is an increasing demand for an expanded color gamut for the toner used for developing electrostatic images (hereinafter simply referred to as "toner") in order to provide printed products with higher customer satisfaction.

[0003] It is generally known that the color gamut of a toner can be expanded by increasing the content of colorant in the toner particles or by increasing the dispersibility of the toner particles to obtain high saturation (see, for example, Patent Documents 1 and 2).

[0004] However, increasing the colorant content in the toner particles inevitably increases the amount of exposed colorant on the surface of the toner particles, resulting in unstable charging of the toner and ultimately in the problem of being unable to form images with high stability.

[0005] In response to the above problem, a cyan toner for developing electrostatic images has been provided that can obtain excellent charging properties and produce a cyan color with high chroma (for example, see Patent Document 3). However, the color gamut that can be output using only high chroma toner lacks low-lightness areas, and the low-lightness areas are supplemented with black toner. In such cases, the output product has a rough texture, and the gloss drops sharply with a change in gradation, making it unsatisfactory where the black toner is applied. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2009-265227 A [Patent Document 2] JP 2009-093161 A [Patent Document 3] JP 2014-26066 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in consideration of the above problems and circumstances, and the problem to be solved is to provide a toner set for developing electrostatic images, an electrophotographic image forming method, and an electrophotographic image forming apparatus, which are capable of obtaining good images in terms of expanding the color gamut in low-lightness areas and smoothing the gloss in medium-lightness areas. [Means for solving the problem]

[0008] In the course of investigating the causes of the above problems in order to solve the above problems, the present inventors discovered that the above problems could be solved by a toner set for developing electrostatic images having a first cyan toner and a second cyan toner each containing a specific compound, and thus arrived at the present invention.

[0009] That is, the above-mentioned problems of the present invention are solved by the following means.

[0010] 1. A toner set for developing electrostatic images, comprising at least two types of cyan toners, The first cyan toner contains a silicon phthalocyanine compound having a structure represented by the following general formula (V), The second cyan toner contains a copper phthalocyanine compound. A toner set for developing electrostatic images, comprising: [ka] [In the formula, Z1, Z2 are R 1、R 2 、R 3 Each of the general formula (IV) is an alkyl group having 1 to 22 carbon atoms. Each of Ra1, Ra2, Ra3, and Ra4 independently represents a substituent. Each of na1, na2, na3, and na4 independently represents an integer of 0 to 4. [ka] [In the formula, R 1 、R 2 and R 3 each independently represents an alkyl group having 1 to 22 carbon atoms, an aryl group having 6 to 18 carbon atoms, an alkoxy group having 1 to 22 carbon atoms, or an aryloxy group having 6 to 18 carbon atoms. 1 、R 2 and R 3 may be the same group or different groups.

[0011] 2. The toner set for developing electrostatic images according to claim 1, wherein the difference in hue angle between the first cyan toner and the second cyan toner at a deposition amount of 3.4 gsm is 10° or more.

[0012] 3. The toner set for developing electrostatic images according to item 1 or 2, wherein the copper phthalocyanine compound has a neutral or basic substituent.

[0013] 4. An electrophotographic image forming method having at least a step of charging an image carrier, a step of forming an electrostatic image, a step of developing the electrostatic image, a step of transferring a toner image, and a step of fixing the toner image, 4. An electrophotographic image forming method, comprising using the toner set for developing an electrostatic image according to any one of items 1 to 3.

[0014] 5. An electrophotographic image forming apparatus comprising at least an image carrier charging means, an electrostatic image forming means, an electrostatic image developing means, a toner image transferring means, and a toner image fixing means, 4. An electrophotographic image forming apparatus, comprising the toner set for developing an electrostatic image according to any one of items 1 to 3. Effect of the Invention

[0015] According to the above-mentioned means of the present invention, it is possible to provide a toner set for developing electrostatic images, an electrophotographic image forming method, and an electrophotographic image forming apparatus, which are capable of obtaining good images in terms of expanding the color gamut in low lightness areas and smoothing the gloss in medium lightness areas.

[0016] Although the mechanism by which the effects of the present invention are expressed or the mechanism by which the effects of the present invention are acted upon has not been clarified, it is speculated as follows.

[0017] In the present invention, by incorporating a cyan toner containing a conventional cyan pigment (copper phthalocyanine compound) into a high chroma cyan toner containing a compound having a structure represented by the above general formula (I) as a toner set for developing electrostatic images, it is possible to obtain, in the cyan image region, an image in which the color gamut on the low lightness side is expanded by the copper phthalocyanine compound, in addition to a high chroma image by the above high chroma cyan toner, and further to provide a toner set for developing electrostatic images that also enables CMYK printing.

[0018] In addition, in the past, when a high chroma cyan toner was used, low brightness gradation was produced with a black toner, resulting in a rapid drop in gloss and lack of smoothness, but by using a compound having a structure represented by the general formula (I) and a conventional cyan toner, it has the advantage of being better in granularity than a black toner, and furthermore, being able to increase gloss by the binder resin in the cyan toner, which is not a binder resin for carbon black (CB). Therefore, by using a conventional cyan toner in combination, it is possible to obtain a toner set for developing electrostatic images that can realize gradation in the medium to low brightness range, which is between the high chroma cyan coloring produced by a silicon phthalocyanine compound, and black coloring, and smooth gloss. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a schematic diagram showing the structure of an electrophotographic image forming apparatus according to the present invention; [Diagram 2] Typical landscape images and CMYK manuscripts for each season used in the examples DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The toner set for developing an electrostatic image of the present invention is a toner set for developing an electrostatic image that is composed of at least two kinds of cyan toners, and the first cyan toner is represented by the general formula ( V The first cyan toner contains a silicon phthalocyanine compound having a structure represented by the formula (I) and the second cyan toner contains a copper phthalocyanine compound. This feature is a technical feature common to or corresponding to the following embodiments.

[0021] As an embodiment of the present invention, from the viewpoint of realizing the effect of the present invention, that is, obtaining a good image in terms of expanding the color gamut in the low lightness area and smoothing the gloss in the medium lightness area, it is preferable that the difference in hue angle between the first cyan toner and the second cyan toner at a deposition amount of 3.4 gsm is 10° or more.

[0022] The hue angle of the high chroma cyan toner containing a silicon phthalocyanine compound is in the range of approximately 210 to 220°, while the hue angle of the cyan toner containing a copper phthalocyanine compound, which is a conventional cyan pigment, is approximately 230 to 240°. Although both are cyan toners, this difference in hue angle is one of the features of the present invention.

[0023] The high chroma cyan toner containing silicon phthalocyanine compound has a chroma C in the range of hue angle 210 to 220 degrees at a deposition amount of 3.4 gsm. * It can produce cyan colors of 56 to 61, helping to expand the color gamut.

[0024] On the other hand, the cyan toner containing the copper phthalocyanine compound has a chroma of C in the range of hue angles of 230 to 240° at a deposition weight of 3.4 gsm. *It can produce cyan colors with a value of 60 to 70, so it can produce greenish colors as well as low-brightness cyan colors that have traditionally been expressed. By combining the above two cyan colors and connecting these gradations, it is possible to create a toner set for developing electrostatic images that can cover a color gamut that was previously not possible to express.

[0025] In addition, it is preferable that the copper phthalocyanine compound has a neutral or basic substituent, from the viewpoint of easily obtaining a desired color gamut.

[0026] The electrophotographic image forming method (hereinafter also referred to as image forming method) of the present invention is an electrophotographic image forming method having at least a step of charging an image carrier, a step of forming an electrostatic image, a step of developing an electrostatic image, a step of transferring a toner image, and a step of fixing a toner image, and is characterized by using the toner set for developing an electrostatic image of the present invention.

[0027] In addition, the electrophotographic image forming apparatus of the present invention (hereinafter also referred to as an end-cap forming apparatus) is an electrophotographic image forming apparatus having at least an image carrier charging means, an electrostatic image forming means, an electrostatic image developing means, a toner image transfer means, and a toner image fixing means, and is characterized in that it uses the toner set for developing electrostatic images of the present invention.

[0028] The present invention, its components, and embodiments for carrying out the present invention will be described in detail below. In this application, the symbol "to" is used to mean that the numerical values ​​before and after the symbol "to" are included as the lower limit and upper limit.

[0029] <<Outline of the toner set for developing electrostatic images of the present invention>> The toner set for developing an electrostatic image of the present invention is a toner set for developing an electrostatic image composed of at least two kinds of cyan toners, the first cyan toner being: before General formula ( V The first cyan toner contains a silicon phthalocyanine compound having a structure represented by the formula:

[0030] Here, the silicon phthalocyanine compound and the copper phthalocyanine compound are generally referred to as "colorants", and "cyan toner" refers to a toner containing a colorant that develops a cyan color. In general, a toner set for developing electrostatic images includes a set of toners containing colorants that develop a cyan (C), magenta (M), yellow (Y), and black (Bk) color. The toner set for developing electrostatic images of the present invention is characterized in that a cyan toner containing a specific compound as a colorant is loaded together with toners containing other colorants.

[0031] From the viewpoint of exerting the effect of the present invention, it is preferable that the difference in hue angle between the first cyan toner and the second cyan toner when the adhesion amount is 3.4 gsm is 10 or more.

[0032] <Hue angle and saturation> Using a commercially available full-color high-speed multifunction printer "bizhub PRO (registered trademark) C8000 (manufactured by Konica Minolta)," in an environment of 20°C temperature and 50% RH, the amount of toner adhesion on the paper was adjusted to 3.4 gsm cyan toner, and an image (a solid image patch measuring 2 cm long x 2 cm wide) was fixed and the color gamut was evaluated.

[0033] The transfer paper used for the evaluation was "POD gloss coated paper 128g / m 2 (Oji Paper Co., Ltd.)" is used. The fixing temperature is set at a temperature of +10°C from the minimum temperature.

[0034] When calculating the hue angle and saturation, * a * b * The "L color system" is used. * The axis direction indicates brightness, and * The axis direction represents the hue in the red-green direction, and b * The axis direction indicates the hue from yellow to blue. * and b *Measurements are taken using a spectrophotometer "Gretag Macbeth Spectrolino" (manufactured by Gretag Macbeth) under conditions of a D50 light source, a measurement wavelength range of 380 to 730 nm in 10 nm intervals, a viewing angle of 2°, a UV-cut filter, and a dedicated white tile for reference alignment.

[0035] In addition, the hue angle h and chroma C * is calculated and evaluated according to the following formula: h = tan-1(b * / a * ) C * =[(a * ) 2 +(b * ) 2 ] 1 / 2

[0036] The toner for developing electrostatic images according to the present invention preferably contains toner base particles containing at least a binder resin and a colorant. In the present invention, the toner base particles to which an external additive has been added are referred to as toner particles, and an aggregate of toner particles is referred to as a toner. Generally, the toner base particles can be used as they are as toner particles, but in the present invention, the toner base particles to which an external additive has been added are used as toner particles.

[0037] The toner base particles used in the present invention contain at least a binder resin, a silicon phthalocyanine compound having a structure represented by the general formula (I), and a copper phthalocyanine compound as colorants, and may further contain other components such as a release agent (wax) and a charge control agent, if necessary.

[0038] Hereinafter, the "toner for developing electrostatic images" according to the present invention will also be simply referred to as "toner" in this specification.

[0039] [1] Toner set for developing electrostatic images The toner set for developing electrostatic images of the present invention is a toner set for developing electrostatic images that is composed of at least two kinds of cyan toners, the first cyan toner containing a silicon phthalocyanine compound having a structure represented by the following general formula (I), and the second cyan toner containing a copper phthalocyanine compound: do.

[0040] [1.1] First cyan toner The first cyan toner according to the present invention contains a silicon phthalocyanine compound having a structure represented by the following general formula (I): do.

[0041] [ka]

[0042] [In the formula, Z1 and Z2 each independently represent a hydroxy group, a chlorine atom, an aryloxy group having 6 to 18 carbon atoms, an alkoxy group having 1 to 22 carbon atoms, or a group represented by the following general formula (IV). Ra1, Ra2, Ra3, and Ra4 each independently represent a substituent. na1, na2, na3, and na4 each independently represent an integer of 0 to 4.]

[0043] In the general formula (I), Z1 and Z2 each independently represent a hydroxyl group, a chlorine atom, an aryloxy group having 6 to 18 carbon atoms, an alkoxy group having 1 to 22 carbon atoms, or a group represented by the following general formula (IV). Ra1, Ra2, Ra3, and Ra4 each independently represent a substituent, and na1, na1, na1, and na1 each independently represent an integer of 0 to 4. Preferred substituents represented by Ra1, Ra2, Ra3, and Ra4 include an alkyl group (e.g., a methyl group, a trifluoromethyl group, an ethyl group, etc.), a halogen atom (e.g., F, Cl, Br, etc.), and a sulfone group. Particularly preferred substituents represented by Ra1, Ra2, Ra3, and Ra4 include a methyl group, a chlorine atom, a trifluoromethyl group, and a sulfone group. It is preferable that na1, na1, na1, and na1 are each independently 1 or 2.

[0044] [ka]

[0045] [In the formula, R 1 , R 2 and R 3 each independently represents an alkyl group having 1 to 22 carbon atoms, an aryl group having 6 to 18 carbon atoms, an alkoxy group having 1 to 22 carbon atoms, or an aryloxy group having 6 to 18 carbon atoms. 1 , R 2 and R 3 may be the same group or different groups.

[0046] R 1 , R 2 and R 3 represents an alkyl group, aryl group, alkoxy group, or aryloxy group having the above carbon numbers, and the carbon number of the alkyl group or alkoxy group is preferably 1 to 10, and more preferably 2 to 8. The carbon number of the aryl group or aryloxy group is preferably 6 to 10, and more preferably 6 to 8.

[0047] A preferred embodiment of the compound having the structure represented by general formula (I) is a compound in which Z1 and Z2 each independently represent a group represented by general formula (IV). 1 , R 2 and R 3 It is also preferred that each of

[0048] Furthermore, the compound having the structure represented by general formula (I) may form a dimer having the structure represented by the following general formula (II).

[0049] [ka]

[0050] [In the formula, Z3 and Z4 each independently represent a hydroxy group, a chlorine atom, an aryloxy group having 6 to 18 carbon atoms, an alkoxy group having 1 to 22 carbon atoms, or a group represented by the above general formula (IV)]

[0051] The toner of the present invention contains a phthalocyanine compound having an axial ligand, which is called a tetraazaporphine compound having a structure represented by the above general formula (I) in which a silicon atom is used as the central metal atom. Here, the axial ligand is represented by Z in the above general formula (I).

[0052] A toner containing a compound having a structure represented by general formula (I) exhibits better color reproducibility than a toner containing a phthalocyanine compound having no axial ligand. In particular, this tendency is remarkable in a toner using a phthalocyanine compound having a structure represented by general formula (I). This is presumably because the compound having a structure represented by general formula (I) has a more complex structure than a phthalocyanine compound having no axial ligand, making it less likely to aggregate or crystallize. As a result, the colorant is uniformly dispersed in the toner particles and fixed images, and color reproducibility is further improved.

[0053] In addition, since the phthalocyanine compound has a structure that makes it less susceptible to aggregation or crystallization, its compatibility with the binder resin in the toner and its solubility in solvents or polymerizable monomers are improved, making it easier for the phthalocyanine compound to be uniformly dispersed in the toner production process, and it is presumed that this results in good color reproducibility.

[0054] In addition, Z1 and Z2 constituting the compound having the structure represented by general formula (I) are preferably groups represented by general formula (IV) among the above-mentioned groups. 1 , R 2 and R 3 is preferably an alkyl group, an aryl group, or an alkoxy group having 1 to 6 carbon atoms, and particularly preferably an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, or a t-butyl group. 1 , R 2 , and R 3may be the same group or different groups.

[0055] In the present invention, the above phthalocyanine compounds can be used alone or in combination of two or more. The content of the above phthalocyanine compounds in the toner is set within the range of 1 to 20% by mass, preferably 1 to 10% by mass, and more preferably 1 to 7% by mass, based on the total mass of the toner. In particular, the above compounds are expected to have high molecular absorptivity, so that even if the amount added is small, it is expected that the effects of the present invention can be achieved.

[0056] Specific examples of tetraazaporphine compounds (phthalocyanine compounds having an axial ligand) having the structure represented by general formula (I) are shown in the table below. vinegar.

[0057] [ka]

[0058] The compound having the structure represented by the general formula (I) according to the present invention can be easily synthesized by known methods. For example, the following patent specifications can be referred to. U.S. Patent No. 5,428,152, U.S. Patent No. 4,927,735, U.S. Patent No. 5,021,563, U.S. Patent No. 5,219,706, U.S. Patent No. 5,034,309, U.S. Patent No. 5,284,943, U.S. Patent No. 5,075,203, U.S. Patent No. 5,484,685, U.S. Patent No. 5,039,600, U.S. Patent No. 5,438,135, U.S. Patent No. 5,665,875, etc.

[0059] [1.2] Second Cyan Toner The second cyan toner according to the present invention is characterized by containing a copper phthalocyanine compound.

[0060] As the copper phthalocyanine compound in the present invention, it is preferable to use an existing substituted copper phthalocyanine compound, but it is also preferable to use an unsubstituted copper phthalocyanine compound, since it is easy to obtain an image with a color in the desired color gamut (lightness and saturation).

[0061] In addition, the composition may contain only a substituted copper phthalocyanine compound, or may contain both a substituted copper phthalocyanine compound and an unsubstituted copper phthalocyanine compound.

[0062] In the case where a substituted copper phthalocyanine compound and an unsubstituted copper phthalocyanine compound are simultaneously contained, the substituted copper phthalocyanine compound becomes a part that disrupts the crystal structure of the copper phthalocyanine compound, and this makes it easier to reduce the primary particle size and control the particle size distribution when producing primary particles of a colorant (copper phthalocyanine compound) by solvent salt milling or the like described below, which is preferable because it makes it easier to control coloring power, color reproducibility, and the like.

[0063] In addition, by containing a substituted copper phthalocyanine compound, the compatibility with the binder resin is improved due to the substituent (functional group) of the substituted copper phthalocyanine compound, and the compound is easily incorporated into the binder resin (improving the dispersibility of the cyan pigment (colorant) throughout the toner). In addition, the term "unsubstituted" as used herein means that the hydrogen atoms on the copper phthalocyanine skeleton are not substituted with a substituent. The term "substituted" means that the hydrogen atoms on the copper phthalocyanine skeleton are substituted with a substituent. In the case of "substitution", it is preferable that the substituted copper phthalocyanine compound has a neutral or basic substituent.

[0064] The unsubstituted copper phthalocyanine compound has crystal forms such as α-type, β-type, and ε-type, and in the present invention, β-type is preferred in terms of hue, color development, stability, and dispersibility. Specifically, β-type includes CI Pigment Blue 15:3, CI Pigment Blue 15:4, etc., α-type includes CI Pigment Blue 15, CI Pigment Blue 15:1, CI Pigment Blue 15:2, etc., and ε-type includes CI Pigment Blue 15:6, etc.

[0065] The substituted copper phthalocyanine compound preferably has a structure represented by the following general formula (a) or (b).

[0066] P-(Y) m (a) P-(AZ) n (b) [In the formula, P represents a residue obtained by removing n hydrogen atoms from a copper phthalocyanine ring. Y represents a primary to tertiary amino group, a carboxy group, a sulfonic acid group, or a salt thereof with a base or a metal. A represents a divalent linking group. Z represents a residue obtained by removing at least one hydrogen atom on a nitrogen atom of a primary or secondary amino group, or a residue obtained by removing at least one hydrogen atom on a nitrogen-containing heterocycle. m represents an integer of 1 to 4, and n represents an integer of 1 to 4.]

[0067] Examples of the secondary and tertiary amino groups include monomethylamino, dimethylamino, and diethylamino groups, and examples of the bases and metals that form salts with the carboxyl and sulfonic acid groups include organic bases such as ammonia, dimethylamine, diethylamine, and triethylamine, and metals such as potassium, sodium, calcium, strontium, and aluminum. Examples of the divalent linking group of A include alkylene groups having 1 to 3 carbon atoms, -CO2-, -SO2-, and -SO2NH(CH2). m - and the like, and Z is, for example, a phthalimido group, a monoalkylamino group, a dialkylamino group, and the like.

[0068] Among these, the substituted copper phthalocyanine compound is preferably substituted with a basic substituent (such as an amino group), since this generates an interaction between the basic substituent and the acid group and ester group of the crystalline polyester resin, thereby improving the controllability of the electrostatic charge.

[0069] The number average major axis of primary particles of the copper phthalocyanine compound in the toner is preferably within a range of 70 to 220 nm, more preferably within a range of 80 to 200 nm, and particularly preferably within a range of 130 to 170 nm.

[0070] The number-average major axis of the primary particles of the copper phthalocyanine compound in the toner is 70 nm or more, which is preferable because it can more reliably prevent the colorant particles from aggregating during toner production, and also increases the coloring power and improves light resistance. Also, the average major axis is 220 nm or less, which is preferable because it can prevent the hue angle from being excessively blue, and also increases the contact area between the colorant particles and the binder resin, so that when a crystalline polyester resin is used as the binder resin, it is possible to reliably control the charging property, which is thought to be due to a change in the domain structure of the crystalline polyester resin.

[0071] The content of the copper phthalocyanine compound in the toner is preferably within a range of 1.0 to 4.0% by mass, more preferably 2.0 to 3.8% by mass, and particularly preferably less than 3.6% by mass.

[0072] The content of the copper phthalocyanine compound in the toner is within the range of 1.0 to 4.0% by mass, so that the content can be reduced without impairing coloring power even with a small amount. In addition, by using such a small amount, the inherent properties of the resin in the toner can be utilized, and even with the same resin composition, low-temperature fixation can be achieved by using the copper phthalocyanine compound.

[0073] Here, as a method for producing the copper phthalocyanine compound, any of the known and commonly used production methods can be adopted.

[0074] (Method of producing copper phthalocyanine compound) As a method for producing a copper phthalocyanine compound, for example, a method called the Wyler method in which phthalic anhydride, urea and a metal salt are reacted to synthesize a metal phthalocyanine, or a method called the phthalonitrile method in which phthalonitrile and a metal salt are reacted to synthesize a metal phthalocyanine can be used.

[0075] Also usable is a method of synthesizing a metal phthalocyanine by reacting phthalic anhydride, urea, and a metal salt in the presence of trimellitic acid, pyromellitic acid, or derivatives thereof such as anhydrides, imides, and esters (see JP-A-61-203175), or a method of synthesizing a metal phthalocyanine by using a paraffinic hydrocarbon solvent and a naphthenic hydrocarbon solvent in combination (see JP-A-8-27388).

[0076] In another embodiment of the method for producing a copper phthalocyanine compound, the copper phthalocyanine compound is prepared by purifying a crude pigment. That is, the copper phthalocyanine compound can be obtained by subjecting the crude pigment to a pigmentation treatment. There is no particular limitation on the pigmentation treatment method, and various pigmentation treatment methods can be adopted. However, it is preferable to adopt a solvent salt milling treatment, which is a method for heating and stirring a crude pigment in a large amount of organic solvent, in that it can suppress significant crystal growth and the aspect ratio of the copper phthalocyanine compound can be easily controlled.

[0077] The solvent salt milling refers to kneading and grinding a crude pigment, an inorganic salt, and an organic solvent. Specifically, the crude pigment, the inorganic salt, and an organic solvent that does not dissolve them are charged into a kneading machine, and kneading and grinding are performed therein. For example, a kneader or a mixer can be used as the kneading machine.

[0078] As the inorganic salt, a water-soluble inorganic salt can be suitably used, and it is preferable to use inorganic salts such as sodium chloride, potassium chloride, sodium sulfate, etc. It is more preferable to use inorganic salts with an average particle size in the range of 0.5 to 50 μm. Such inorganic salts can be easily obtained by finely grinding ordinary inorganic salts.

[0079] The amount of the inorganic salt used is preferably within a range of 6 to 20 parts by mass, and more preferably within a range of 8 to 15 parts by mass, per part by mass of the crude pigment.

[0080] As the organic solvent, a water-soluble organic solvent that can suppress crystal growth can be suitably used, such as diethylene glycol, glycerin, ethylene glycol, propylene glycol, liquid polyethylene glycol, liquid polypropylene glycol, 2-(methoxymethoxy)ethanol, 2-butoxyethanol, 2-(isopentyloxy)ethanol, 2-(hexyloxy)ethanol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, triethylene glycol, triethylene glycol monomethyl ether, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol, etc.

[0081] The amount of the water-soluble organic solvent used is not particularly limited, but is preferably 0.01 to 15 parts by mass per part by mass of the crude pigment.

[0082] In obtaining the copper phthalocyanine compound used in the present invention, only a crude pigment of an unsubstituted copper phthalocyanine compound may be subjected to solvent salt milling, or a crude pigment of an unsubstituted copper phthalocyanine compound and a substituted copper phthalocyanine compound may be used in combination to be subjected to solvent salt milling.

[0083] The copper phthalocyanine compound obtained by using a crude pigment of an unsubstituted copper phthalocyanine compound in combination with a substituted copper phthalocyanine compound and subjecting it to solvent salt milling is a copper phthalocyanine compound containing an unsubstituted copper phthalocyanine compound and a substituted copper phthalocyanine compound. The copper phthalocyanine compound including the unsubstituted copper phthalocyanine compound and the substituted copper phthalocyanine compound as a whole is preferably within the following average aspect ratio range. Here, the "average aspect ratio" refers to the ratio (Db / Da) of the number average major axis Db to the number average minor axis Da of the primary particles of the copper phthalocyanine compound.

[0084] In the present invention, the average aspect ratio is preferably within a range of 3.0 to 6.0. By having the average aspect ratio of 3.0 or more, even if the primary particle size is small, the colorant particles can be present in a dispersed state in the raw colorant particle dispersion liquid and in the toner, and sufficient coloring power can be obtained with a small colorant content, resulting in a toner with high saturation. In addition, by having the average aspect ratio of 6.0 or less, the hue angle can be prevented from becoming excessively blue, resulting in a toner that can ensure an image with a desired color gamut (brightness and saturation).

[0085] From the viewpoint of improving the coloring power of the toner, the average aspect ratio of the primary particles of the copper phthalocyanine compound in the toner is preferably within a range of 3.0 to 5.0, and more preferably within a range of 3.5 to 4.5.

[0086] The average aspect ratio can be controlled within the range of 3.0 to 6.0 by controlling the type of solvent, temperature, precipitation rate, dispersion, and other conditions during crystallization in the production process of the copper phthalocyanine compound.

[0087] The amount of the substituted copper phthalocyanine compound that can be included in the crude pigment during the solvent salt milling is usually within the range of 0.01 to 0.3 parts by mass per part by mass of the crude pigment. The average aspect ratio and the axis length of the primary particles can be controlled by adjusting the content of the substituted copper phthalocyanine compound. For example, the greater the content of the substituted copper phthalocyanine compound, the shorter the length of the major axis and the smaller the average aspect ratio.

[0088] The temperature during the solvent salt milling is preferably within the range of 30 to 150° C., more preferably within the range of 50 to 100° C., and particularly preferably within the range of 60 to 95° C. The time for the solvent salt milling is preferably 5 to 20 hours, and more preferably 5 to 18 hours.

[0089] When the conditions other than the kneading time during the solvent salt milling are kept constant, the aspect ratio and axis length can be controlled by adjusting the kneading time. Specifically, the longer the kneading time, the shorter the major axis length and the smaller the average aspect ratio.

[0090] [1.3] Binder resin The binder resin constituting the toner according to the present invention preferably contains an amorphous resin and a crystalline polyester resin.

[0091] (Crystalline polyester resin) The crystalline polyester resin is a known polyester resin obtained by polycondensation reaction of a divalent or higher carboxylic acid (polyvalent carboxylic acid component) and / or a hydroxycarboxylic acid with a divalent or higher alcohol (polyhydric alcohol component), and has a clear melting peak in differential scanning calorimetry (DSC) instead of a stepwise change in endothermic heat. Specifically, the clear melting peak means a peak whose half-width in the second heating process is within 15°C in the DSC curve obtained by differential scanning calorimetry of the above-mentioned crystalline polyester resin alone.

[0092] The melting point of the crystalline polyester resin is preferably in the range of 65 to 85°C, more preferably in the range of 75 to 85°C. By having the melting point of the crystalline polyester resin in the above range, sufficient low-temperature fixability and excellent image storage stability can be obtained. The melting point of the crystalline polyester resin can be controlled by the resin composition. Here, the melting point of the crystalline polyester resin is the peak top temperature of the melting peak in the second heating process in the DSC curve obtained by differential scanning calorimetry of the above-mentioned crystalline polyester resin alone. In addition, when there are multiple melting peaks in the DSC curve, the peak top temperature of the melting peak with the largest amount of heat absorption is taken as the melting point.

[0093] The melting point (Tm) of the crystalline polyester resin is the temperature at the peak top of the endothermic peak, and can be measured by DSC using Diamond DSC (manufactured by PerkinElmer). Specifically, the sample is sealed in an aluminum pan KIT No. B0143013, set in the sample holder of a thermal analysis device Diamond DSC (manufactured by PerkinElmer), and the temperature is changed in the order of heating, cooling, and heating. In the first heating, the temperature is raised from room temperature (25°C), and in the second heating, the temperature is raised from 0°C at a heating rate of 10°C / min to 150°C, and 150°C is held for 5 minutes, and in the cooling, the temperature is lowered from 150°C to 0°C at a heating rate of 10°C / min, and the temperature of 0°C is held for 5 minutes. The temperature at the peak top of the endothermic peak in the endothermic curve obtained in the second heating is measured as the melting point.

[0094] The polycarboxylic acid component for forming the crystalline polyester resin is a compound containing two or more carboxy groups in one molecule.Specific examples include saturated aliphatic dicarboxylic acids such as succinic acid, sebacic acid, and dodecanedioic acid; alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid; aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid; trivalent or higher polycarboxylic acids such as trimellitic acid and pyromellitic acid; and anhydrides or alkyl esters having 1 to 3 carbon atoms of these carboxylic acid compounds.As the polycarboxylic acid component for forming the crystalline polyester resin, it is preferable to use saturated aliphatic dicarboxylic acids.These may be used alone or in combination of two or more.

[0095] The polyhydric alcohol component for forming the crystalline polyester resin is a compound containing two or more hydroxyl groups in one molecule. Specifically, for example, aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, neopentyl glycol, and 1,4-butenediol; trihydric or higher polyhydric alcohols such as glycerin, pentaerythritol, trimethylolpropane, and sorbitol, etc. are included. As the polyhydric alcohol component for forming the crystalline polyester resin, it is preferable to use an aliphatic diol. These may be used alone or in combination of two or more.

[0096] The method for producing the crystalline polyester resin is not particularly limited, and the resin can be produced using a general polyester polymerization method in which the above-mentioned polyvalent carboxylic acid and polyhydric alcohol are reacted in the presence of a catalyst. For example, it is preferable to produce the resin by using a direct polycondensation method or an ester exchange method depending on the type of monomer.

[0097] In addition, a linear aliphatic hydroxycarboxylic acid can be used in combination with the polyvalent carboxylic acid and / or polyhydric alcohol. Examples of linear aliphatic hydroxycarboxylic acids for forming a crystalline polyester resin include 5-hydroxypentanoic acid, 6-hydroxyhexanoic acid, 7-hydroxypentanoic acid, 8-hydroxyoctanoic acid, 9-hydroxynonanoic acid, 10-hydroxydecanoic acid, 12-hydroxydodecanoic acid, 14-hydroxytetradecanoic acid, 16-hydroxyhexadecanoic acid, 18-hydroxyoctadecanoic acid, and lactone compounds cyclized from these hydroxycarboxylic acids, or alkyl esters with alcohols having 1 to 3 carbon atoms. These may be used alone or in combination of two or more.

[0098] Furthermore, when forming the crystalline polyester resin, it is preferable to use a polyvalent carboxylic acid and a polyhydric alcohol component, since this makes it easy to control the reaction and allows a resin having a desired molecular weight to be obtained.

[0099] Examples of catalysts that can be used in the production of crystalline polyester resins include titanium catalysts such as titanium tetraethoxide, titanium tetrapropoxide, titanium tetraisopropoxide, and titanium tetrabutoxide, and tin catalysts such as dibutyltin dichloride, dibutyltin oxide, and diphenyltin oxide.

[0100] The use ratio of the polyvalent carboxylic acid component and the polyhydric alcohol component is preferably such that the equivalent ratio [OH] / [COOH] of the hydroxyl group [OH] of the polyhydric alcohol component to the carboxyl group [COOH] of the polyvalent carboxylic acid component is within the range of 1.5 / 1 to 1 / 1.5, more preferably 1.2 / 1 to 1 / 1.2.

[0101] The acid value of the crystalline polyester resin is preferably within the range of 5 to 30 mgKOH / g, more preferably 10 to 25 mgKOH / g, and even more preferably 15 to 25 mgKOH / g. This acid value is the mass of potassium hydroxide (KOH) required to neutralize the acid contained in 1 g of a sample, expressed in mg units. The acid value of the resin is measured according to the following procedure in accordance with JIS K0070-1992.

[0102] (Preparation of reagents) Dissolve 1.0 g of phenolphthalein in 90 mL of ethyl alcohol (95% by volume), add ion-exchanged water to make 100 mL, and prepare a phenolphthalein solution. Dissolve 7 g of JIS special grade potassium hydroxide in 5 mL of ion-exchanged water, and add ethyl alcohol (95% by volume) to make 1 liter. Place in an alkali-resistant container to avoid contact with carbon dioxide, leave for 3 days, then filter to prepare a potassium hydroxide solution. Standardization follows the description of JIS K0070-1992.

[0103] (Actual test) Weigh out 2.0 g of the crushed sample into a 200 mL Erlenmeyer flask, add 100 mL of a toluene / ethanol (toluene:ethanol volume ratio 2:1) mixture, and dissolve for 5 hours. Next, add a few drops of the prepared phenolphthalein solution as an indicator, and titrate with the prepared potassium hydroxide solution. The end point of the titration is when the indicator remains a pale red color for about 30 seconds.

[0104] (Blank test) The same procedure as in the main test described above is carried out, except that no sample is used (i.e., only a mixed solution of toluene / ethanol (toluene:ethanol in a volume ratio of 2:1) is used).

[0105] The titration results of the main test and the blank test are substituted into the following formula (1) to calculate the acid value.

[0106] Formula (1) A=[(CB)×f×5.6] / S A: Acid value (mgKOH / g) B: Amount of potassium hydroxide solution added during blank test (mL) C: Amount of potassium hydroxide solution added during this test (mL) f: Factor of 0.1 mol / L potassium hydroxide ethanol solution S: mass of sample (g)

[0107] The molecular weight of the crystalline polyester resin is preferably such that the weight average molecular weight (Mw) is within the range of 5,000 to 50,000 and the number average molecular weight (Mn) is within the range of 1,500 to 25,000, calculated from the molecular weight distribution measured by gel permeation chromatography (GPC).

[0108] The molecular weight measurement by GPC is carried out as follows.

[0109] That is, using the apparatus "HLC-8320" (manufactured by Tosoh Corporation) and the columns "TSKgel guardcolumn SuperHZ-L" and "TSKgel SuperHZM-M" (manufactured by Tosoh Corporation), tetrahydrofuran (THF) is passed as a carrier solvent at a flow rate of 0.2 ml / min while maintaining the column temperature at 40°C. The measurement sample (crystalline polyester resin) is dissolved in tetrahydrofuran to a concentration of 1 mg / ml under dissolution conditions of treatment for 5 minutes using an ultrasonic disperser at room temperature, and then treated with a membrane filter with a pore size of 0.2 μm to obtain a sample solution. 10 μL of this sample solution is injected into the apparatus together with the above carrier solvent, detected using a refractive index detector (RI detector), and the molecular weight distribution of the measurement sample is calculated using a calibration curve measured using monodisperse polystyrene standard particles.

[0110] The standard polystyrene sample for calibration curve measurement was a 6×10 molecular weight polystyrene manufactured by Pressure Chemical. 2 , 2.1×10 3 , 4×10 3 , 1.75×10 4 , 5.1×10 4 , 1.1×10 5 , 3.9×10 5 , 8.6×10 5 , 2×10 6 , 4.48×10 6 At least 10 standard polystyrene samples are measured using the above and a calibration curve is created.

[0111] The content of the crystalline polyester resin in the binder resin is preferably within a range of 5 to 20% by mass, and more preferably within a range of 5 to 10% by mass. By making the content of the crystalline polyester resin in the binder resin 5% by mass or more, sufficient low-temperature fixability can be reliably obtained. Furthermore, by making the content of the crystalline polyester resin in the binder resin 20% by mass or less, the crystalline polyester resin can be reliably introduced into the toner during toner production.

[0112] As the crystalline polyester resin, a styrene-acrylic modified crystalline polyester resin in which a styrene-acrylic polymerized segment and a crystalline polyester polymerized segment are bonded may be used.

[0113] Here, "styrene-acrylic modified crystalline polyester resin" refers to a resin composed of polyester molecules with a block copolymer structure, in which a styrene-acrylic copolymer molecular chain (styrene-acrylic polymerization segment) is chemically bonded to a crystalline polyester molecular chain (crystalline polyester polymerization segment).

[0114] The method for forming the crystalline polyester polymer segment is not particularly limited. The specific types of polyvalent carboxylic acid and polyhydric alcohol used in forming the polymer segment and the polycondensation conditions of these monomers are the same as those described above, so the description will be omitted here.

[0115] On the other hand, the styrene-acrylic polymerized segment constituting the styrene-acrylic modified crystalline polyester resin is formed by addition polymerization of at least a styrene monomer and a (meth)acrylic acid ester monomer. The styrene monomer and the (meth)acrylic acid ester monomer used are not particularly limited, but for example, one or more types selected from the following may be used.

[0116] (1) Styrene monomer Styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-phenylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, pn-dodecylstyrene and their derivatives, etc.; (2) (Meth)acrylic acid ester monomer Methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate (n-butyl (meth)acrylate), isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-stearyl (meth)acrylate, dodecyl (meth)acrylate, phenyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and derivatives thereof; In this specification, the term "(meth)acrylic acid" includes both acrylic acid and methacrylic acid.

[0117] The styrene-acrylic polymer segment may be formed by using the following monomers in addition to the above monomers.

[0118] (3) Vinyl esters Vinyl propionate, vinyl acetate, vinyl benzoate, etc.; (4) Vinyl ethers Vinyl methyl ether, vinyl ethyl ether, etc.; (5) Vinyl ketones Vinyl methyl ketone, vinyl ethyl ketone, vinyl hexyl ketone, etc.; (6) N-vinyl compounds N-vinylcarbazole, N-vinylindole, N-vinylpyrrolidone, etc.; (7) Other monomers Vinyl compounds such as vinylnaphthalene and vinylpyridine; acrylic acid or methacrylic acid derivatives such as acrylonitrile, methacrylonitrile and acrylamide; and the like.

[0119] The method for forming the styrene-acrylic polymer segment is not particularly limited, and examples thereof include a method in which polymerization is carried out by a known polymerization method such as bulk polymerization, solution polymerization, emulsion polymerization, mini-emulsion, or dispersion polymerization using any polymerization initiator commonly used in the polymerization of the above-mentioned monomers, such as peroxides, persulfides, persulfates, or azo compounds.

[0120] The content of the crystalline polyester polymer segment in the styrene-acrylic modified crystalline polyester resin is not particularly limited, but is preferably within the range of 60 to 99 mass%, and more preferably within the range of 70 to 98 mass%, relative to 100 mass% of the styrene-acrylic modified polyester resin.

[0121] The content of the styrene-acrylic polymerized segment in the styrene-acrylic modified crystalline polyester resin (hereinafter also referred to as the "styrene-acrylic modification amount") is not particularly limited, but is preferably within the range of 1 to 40 mass%, and more preferably within the range of 2 to 30 mass%, relative to 100 mass% of the styrene-acrylic modified crystalline polyester resin.

[0122] Specifically, the amount of styrene-acrylic modification refers to the ratio of the combined mass of styrene monomer and (meth)acrylic ester monomer to the total mass of resin materials used to synthesize styrene-acrylic modified crystalline polyester resin, i.e., the combined mass of monomers used to synthesize unmodified crystalline polyester resin that becomes the crystalline polyester polymerization segment, styrene monomer and (meth)acrylic ester monomer that become the styrene-acrylic polymerization segment, and bireactive monomers that bind these.

[0123] Here, the "ambireactive monomer" is a monomer that bonds a styrene-acrylic polymerization segment and a crystalline polyester polymerization segment, and has, in the molecule, both a group selected from a hydroxy group, a carboxy group, an epoxy group, a primary amino group, and a secondary amino group that forms a crystalline polyester polymerization segment, and an ethylenically unsaturated group that forms a styrene-acrylic polymerization segment.

[0124] Specific examples of the bireactive monomer include acrylic acid, methacrylic acid, fumaric acid, maleic acid, etc., and furthermore, esters of these hydroxyalkyls (having 1 to 3 carbon atoms) may be used, but from the viewpoint of reactivity, acrylic acid, methacrylic acid, or fumaric acid is preferred. The styrene-acrylic polymerized segment and the crystalline polyester polymerized segment are bonded via this bireactive monomer.

[0125] From the viewpoint of improving low-temperature fixing ability, the amount of the bireactive monomer used is preferably within a range of 1 to 20% by mass, with the total amount of the monomers constituting the styrene-acrylic polymer segment being 100% by mass.

[0126] The method for producing the styrene-acrylic modified crystalline polyester resin is not particularly limited as long as it is a method capable of forming a polymer having a structure in which a crystalline polyester polymer segment and a styrene-acrylic polymer segment are chemically bonded. Specific examples of the method for producing the styrene-acrylic modified crystalline polyester resin include the following methods.

[0127] (A) A method in which a crystalline polyester polymer segment is polymerized in advance, a bireactive monomer is reacted with the crystalline polyester polymer segment, and a styrene monomer and a (meth)acrylic acid ester monomer for forming a styrene-acrylic polymer segment are further reacted to form the styrene-acrylic polymer segment; (B) A method in which a styrene-acrylic polymerized segment is polymerized in advance, the styrene-acrylic polymerized segment is reacted with a bireactive monomer, and further reacted with a polyvalent carboxylic acid and a polyhydric alcohol for forming a crystalline polyester polymerized segment, thereby forming a crystalline polyester polymerized segment; (C) A method in which the crystalline polyester polymer segment and the styrene-acrylic polymer segment are polymerized in advance, and then reacted with a bireactive monomer to bond the two.

[0128] Among the above formation methods (A) to (C), the method (A) is preferred from the viewpoint of simplifying the production process.

[0129] <Amorphous resin> In the present invention, the amorphous resin may be an amorphous polyester resin or an amorphous vinyl resin.

[0130] The term "amorphous resin" refers to a resin that does not show a clear endothermic peak in differential scanning calorimetry (DSC). In other words, it usually does not have a melting point (a clear endothermic peak in a DSC curve measured using a differential scanning calorimetry (DSC) measuring device) and has a relatively high glass transition point (Tg). More specifically, the Tg of the amorphous resin measured by a differential scanning calorimetry device is preferably within a range of 35 to 70°C, more preferably within a range of 50 to 65°C. By having the Tg of the amorphous resin be 35°C or higher, it is possible to impart sufficient thermal strength to the toner, and sufficient heat-resistant storage stability can be obtained. In addition, by having the Tg of the amorphous resin be 70°C or lower, sufficient low-temperature fixability can be reliably obtained.

[0131] The Tg of the amorphous resin is measured by the method (DSC method) specified in ASTM (American Society for Testing and Materials) D3418-82. That is, 4.5 mg of the measurement sample (amorphous resin) is precisely weighed to two decimal places, sealed in an aluminum pan, and set in the sample holder of a differential scanning calorimeter "DSC8500" (manufactured by PerkinElmer). An empty aluminum pan is used as a reference, and temperature control is performed with a measurement temperature of -10 to 120°C, a heating rate of 10°C / min, and a cooling rate of 10°C / min, with heating-cooling-heating, and analysis is performed based on the data from the second heating. The value of the intersection between the extension line of the baseline before the rise of the first endothermic peak and the tangent line showing the maximum slope from the rising part of the first endothermic peak to the peak apex is taken as the glass transition point.

[0132] The molecular weight of the amorphous resin measured by gel permeation chromatography (GPC) is preferably within the range of a number average molecular weight (Mn) of 1500 to 25000 and a weight average molecular weight (Mw) of 10000 to 80000. By having the molecular weight of the amorphous resin within the above range, sufficient low-temperature fixability and excellent heat-resistant storage stability can be reliably achieved. The molecular weight measurement of the amorphous resin by GPC is performed in the same manner as above, except that an amorphous resin is used as the measurement sample.

[0133] (Amorphous polyester resin) The amorphous polyester resin is a polyester resin other than the crystalline polyester resin.

[0134] The acid value of the amorphous polyester resin is preferably within the range of 5 to 45 mgKOH / g, more preferably within the range of 5 to 30 mgKOH / g. If the acid value is 45 mgKOH / g or less, it is preferable in that the hygroscopicity is not increased and the chargeability can be prevented from decreasing even under high humidity. If the acid value is 5 mgKOH / g or more, it is preferable in that the dispersion stability of the resin particles can be maintained and the toner can be easily produced. The acid value can be determined in the same manner as described in the explanation of the crystalline polyester resin.

[0135] The amorphous polyester resin may be one type of amorphous polyester resin, or a mixture of two or more types of amorphous polyester resins.

[0136] The amorphous polyester resin may be a known polyester resin. The amorphous polyester resin is synthesized from a polyvalent carboxylic acid component and a polyhydric alcohol component. The amorphous polyester resin may be a commercially available product or a synthesized product.

[0137] As the polyhydric alcohol component, for example, diols such as ethylene glycol, propylene glycol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, bisphenol A, hydrogenated bisphenol A, BPA-PO (propylene oxide n mole adduct of bisphenol A), and BPA-EO (ethylene oxide n mole adduct of bisphenol A) can be used. In addition, for example, trihydric or higher alcohols such as glycerin, sorbitol, 1,4-sorbitan, and trimethylolpropane can be used. Among these, bisphenol A, hydrogenated bisphenol A, BPA-PO, or BPA-EO are preferred, BPA-PO or BPA-EO are more preferred, and propylene oxide 2 mole adduct of bisphenol A or ethylene oxide 2 mole adduct of bisphenol A are even more preferred. These may be used alone or in combination of two or more.

[0138] Examples of the polycarboxylic acid component include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and naphthalenedicarboxylic acid; aliphatic saturated dicarboxylic acids such as succinic acid, alkenylsuccinic acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid; aliphatic unsaturated dicarboxylic acids such as maleic acid, maleic acid, fumaric acid, itaconic acid, itaconic anhydride, citraconic acid, citraconic acid, and mesaconic acid; alicyclic polycarboxylic acids such as cyclohexanedicarboxylic acid; salts thereof, lower alkyl esters, and acid anhydrides thereof. Among these, aromatic dicarboxylic acids, their salts, lower alkyl esters, and acid anhydrides are preferred, and terephthalic acid, phthalic acid, their salts, lower alkyl esters, and acid anhydrides are more preferred. These polyvalent carboxylic acid components may be used alone or in combination of two or more.

[0139] By including a trivalent or higher carboxylic acid as the polyvalent carboxylic acid component, the polymer chain can have a crosslinked structure, and by forming the crosslinked structure, it is possible to obtain the further effect of fixing the crystalline polyester resin once it has become compatible with the amorphous polyester resin, making it difficult for the resin to separate.

[0140] Examples of trivalent or higher carboxylic acids include trimellitic acids such as 1,2,4-benzenetricarboxylic acid and 1,2,5-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, hemimellitic acid, trimesic acid, mellophanic acid, prenic acid, pyromellitic acid, mellitic acid, 1,2,3,4-butanetetracarboxylic acid, salts thereof, lower alkyl esters and acid anhydrides thereof, with trimellitic acid, its salts, lower alkyl esters and acid anhydrides being particularly preferred.

[0141] When the polycarboxylic acid component contains a dicarboxylic acid and a tri- or higher carboxylic acid, the amount of the tri- or higher carboxylic acid added is preferably within the range of 1 to 30 mol %, more preferably within the range of 5 to 20 mol %, and more preferably within the range of 10 to 15 mol %, based on the total number of moles of the polycarboxylic acid component.

[0142] The polyvalent carboxylic acid component may contain, in addition to the above-mentioned compounds, a dicarboxylic acid component having a sulfonic acid group.

[0143] The production of the amorphous polyester resin is not particularly limited, but is preferably carried out by a polycondensation reaction between a polyvalent carboxylic acid component and a polyhydric alcohol component at a polymerization temperature of 180 to 260° C., and if necessary, the reaction system is decompressed to remove water and alcohol generated during the condensation. The polymerization time is not particularly limited, but is preferably 1 to 10 hours, and more preferably 2 to 6 hours.

[0144] If the polymerizable monomers (polyvalent carboxylic acid component, polyhydric alcohol component) are not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a dissolution aid to dissolve them. The polycondensation reaction is carried out while distilling off the dissolution aid. If a polymerizable monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the poorly compatible polymerizable monomer and the polymerizable monomer be condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.

[0145] Examples of catalysts that can be used in the production of amorphous polyester resin include alkali metal compounds containing sodium, lithium, etc.; Group 2 metal compounds containing magnesium, calcium, etc.; metal compounds containing zinc, manganese, antimony, titanium, tin, zirconium, germanium, etc.; phosphorous compounds; phosphoric acid compounds; and amine compounds. These may be used alone or in combination of two or more. Among these, from the viewpoint of making Mw / Mn smaller, metal compounds containing zinc, manganese, antimony, titanium, tin, zirconium, germanium, etc. are preferred, and metal compounds of tin (tin-based catalysts) are more preferred. Tin-based catalysts are not particularly limited, but examples include dibutyltin oxide, etc.

[0146] The amount of catalyst added is not particularly limited, but is preferably within the range of 0.00001 to 10 mass% based on the total amount of polycarboxylic acid. When the amount of catalyst added is increased, the reaction can proceed more reliably, and when the amount of catalyst added is decreased, it is more economical.

[0147] The content of the amorphous polyester resin is preferably 5 to 30% by mass, more preferably 5 to 20% by mass, of the total binder resin. When the content is within this range, the toner obtained has excellent blocking resistance and low-temperature fixability.

[0148] (amorphous vinyl resin) The amorphous vinyl resin is not particularly limited as long as it is a polymer of a vinyl compound, and examples thereof include acrylate resin, styrene-(meth)acrylate resin, ethylene-vinyl acetate resin, etc. These may be used alone or in combination of two or more.

[0149] Among the above amorphous vinyl resins, styrene-(meth)acrylic acid ester resins (hereinafter also referred to as "styrene-acrylic resins") are preferred in terms of plasticity during thermal fixing. Therefore, the following will explain styrene-acrylic resins as amorphous vinyl resins.

[0150] Styrene-acrylic resin is formed by addition polymerization of at least styrene monomer and (meth)acrylic acid ester monomer. The styrene monomer referred to here includes not only styrene represented by the structural formula CH2=CH-C6H5, but also those having a structure with a known side chain or functional group in the styrene structure. The (meth)acrylic acid ester monomer referred to here includes not only acrylic acid ester and methacrylic acid ester represented by the structural formula CH2=CHCOOR (R is an alkyl group), but also esters having a known side chain or functional group in the structure of acrylic acid ester derivatives and methacrylic acid ester derivatives.

[0151] Specific examples of styrene monomers and (meth)acrylic acid ester monomers capable of forming styrene-acrylic resins are shown below, but the monomers used in the present invention are not limited to the following.

[0152] Specific examples of styrene monomers include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-phenylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, pn-dodecylstyrene, etc. These styrene monomers can be used alone or in combination of two or more.

[0153] Specific examples of the (meth)acrylic acid ester monomer include acrylic acid ester monomers such as methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, tert-butyl acrylate, isobutyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, lauryl acrylate, and phenyl acrylate; and methacrylic acid ester monomers such as methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, lauryl methacrylate, phenyl methacrylate, diethylaminoethyl methacrylate, and dimethylaminoethyl methacrylate. These acrylic acid ester monomers or methacrylic acid ester monomers can be used alone or in combination of two or more. That is, it is possible to form a copolymer using a styrene monomer and two or more acrylate monomers, to form a copolymer using a styrene monomer and two or more methacrylate monomers, or to form a copolymer using a styrene monomer in combination with an acrylate monomer and a methacrylate monomer.

[0154] The content of structural units derived from styrene monomers in the styrene-acrylic resin is preferably within a range of 60 to 85% by mass relative to the total amount of the styrene-acrylic resin, and the content of structural units derived from (meth)acrylic acid ester monomers in the styrene-acrylic resin is preferably within a range of 15 to 40% by mass relative to the total amount of the styrene-acrylic resin.

[0155] Furthermore, in addition to the above-mentioned styrene monomer and (meth)acrylic acid ester monomer, the styrene-acrylic resin may be addition polymerized with compounds having a carboxy group, such as acrylic acid, methacrylic acid, maleic acid, itaconic acid, cinnamic acid, fumaric acid, maleic acid monoalkyl ester, and itaconic acid monoalkyl ester; and compounds having a hydroxy group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and polyethylene glycol mono(meth)acrylate.

[0156] The content of the structural units derived from the above compounds in the styrene-acrylic resin is preferably within a range of 0.1 to 15 mass % relative to the total amount of the styrene-acrylic resin.

[0157] The content of the amorphous vinyl resin is preferably within a range of 40 to 95% by mass, more preferably 60 to 90% by mass, of the total binder resin. In such a range, the toner obtained has a high degree of freedom in resin design and is easy to control the charge.

[0158] [1.4] Other ingredients <Coloring agent> As the colorant other than the above-mentioned cyan colorant used in the toner for developing electrostatic images of the present invention, typical examples of the colorant include colorants for each of the colors magenta (M), yellow (Y), black (Bk) and white (W).

[0159] Examples of colorants for magenta include dyes such as CI Solvent Red 1, 49, 52, 58, 63, 111, and 122, and pigments such as CI Pigment Red 2, 3, 5, 6, 7, 15, 16, 48:1, 53:1, 57:1, 60, 63, 64, 68, 81, 83, 87, 88, 89, 90, 112, 114, 122, 123, 139, 144, 149, 150, 163, 166, 170, 177, 178, 184, 202, 206, 207, 209, 222, 238, and 269.

[0160] In the present invention, the use of a colorant for high chroma magenta is a preferred embodiment for obtaining a toner set that can provide images with a good color gamut and smooth gloss.

[0161] As a colorant for high chroma magenta, for example, a complex compound having a structure represented by chemical formulas (3) to (6) described in JP2010-007963A, a complex compound having a structure represented by general formula (1) described in JP2010-054799A, a complex compound having a structure represented by general formula (1) described in JP2010-054800A, a combination of a dye compound having a structure represented by general formula (1) and a copper complex compound having a structure represented by general formula (2) described in JP2015-169697A, or a colorant that is a chelate compound of a complex compound having a structure represented by general formula (1) and a dye compound having a structure represented by general formula (2) described in JP2016-130225A, and the like are preferably used.

[0162] Examples of colorants for yellow include dyes such as CI Solvent Yellow 19, 44, 77, 79, 81, 82, 93, 98, 103, 104, 112, and 162, and pigments such as CI Pigment Orange 31, 43, CI Pigment Yellow 12, 14, 15, 17, 74, 83, 93, 94, 138, 155, 162, 180, and 185.

[0163] Examples of the colorant for black include carbon black alone or a colorant containing magnetic particles. Examples of carbon black include channel black, furnace black, acetylene black, thermal black, and lamp black. Examples of the magnetic material of the magnetic particles include ferromagnetic metals such as iron, nickel, and cobalt; alloys containing these metals, and compounds of ferromagnetic metals such as ferrite and magnetite; chromium dioxide; and alloys that do not contain ferromagnetic metals but exhibit ferromagnetism by heat treatment. Examples of alloys that exhibit ferromagnetism by heat treatment include Heusler alloys such as manganese-copper-aluminum and manganese-copper-tin.

[0164] Examples of colorants for white include inorganic pigments (e.g., titanium white, zinc white, titanium strontium white, heavy calcium carbonate, light calcium carbonate, titanium dioxide, aluminum hydroxide, satin white, talc, calcium sulfate, barium sulfate, zinc oxide, magnesium oxide, magnesium carbonate, amorphous silica, colloidal silica, white carbon, kaolin, calcined kaolin, delaminated kaolin, aluminosilicate, sericite, bentonite, smexite, etc.), and organic pigments (e.g., polystyrene resin particles, urea formalin resin particles, etc.).

[0165] The content of the above colorant in the toner base particles can be determined appropriately and independently. For example, from the viewpoint of ensuring color reproducibility of the image, the content is preferably within the range of 1 to 30% by mass, and more preferably within the range of 2 to 20% by mass.

[0166] The particle size of the colorant, in terms of volume average particle size, is preferably within the range of, for example, 10 to 1000 nm, more preferably within the range of 50 to 500 nm, and even more preferably within the range of 80 to 300 nm.

[0167] The volume average particle diameter may be a catalog value, and for example, the volume average particle diameter (volume-based median diameter) of the colorant can be measured using "UPA-150" (manufactured by Microtrack Bell Co., Ltd.).

[0168] <Release agent> The toner according to the present invention may contain a releasing agent. As the releasing agent, various known waxes can be used.

[0169] Specific examples of such waxes include polyolefin waxes such as polyethylene wax and polypropylene wax; branched-chain hydrocarbon waxes such as microcrystalline wax; long-chain hydrocarbon waxes such as paraffin wax and sazol wax; dialkyl ketone waxes such as distearyl ketone; ester waxes such as carnauba wax, montan wax, behenyl behenate, trimethylolpropane tribehenate, pentaerythritol tetrabehenate, pentaerythritol diacetate dibehenate, glycerin tribehenate, 1,18-octadecanediol distearate, tristearyl trimellitate, and distearyl maleate; and amide waxes such as ethylenediamine behenylamide and tristearyl trimellitate.

[0170] It is preferable to use a release agent that does not have any interaction, such as being compatible with the resin constituting the binder resin.

[0171] Among these, from the viewpoint of releasability during low-temperature fixing, it is preferable to use a release agent having a low melting point, specifically, a melting point within a range of 60 to 100° C. In addition, it is preferable to use a release agent having a melting point of about (Mp1-10)° C. to (Mp1+20)° C., where Mp1 is the melting point of the crystalline polyester resin constituting the binder resin.

[0172] The content of the release agent in the toner is preferably within a range of 1 to 20% by mass, more preferably within a range of 5 to 20% by mass. By having the content of the release agent in the toner within the above range, both separation property and fixability can be reliably achieved.

[0173] A method of introducing the release agent into the toner includes a method in which particles consisting of only the release agent are aggregated and fused together with amorphous resin particles, crystalline polyester resin particles, etc. in an aqueous medium in the aggregation and fusion process of the toner manufacturing method described later. The release agent particles can be obtained as a dispersion liquid in which the release agent is dispersed in an aqueous medium. The dispersion liquid of the release agent particles can be prepared by heating an aqueous medium containing a surfactant to a temperature higher than the melting point of the release agent, adding the molten release agent solution, applying mechanical energy such as mechanical stirring or ultrasonic energy to finely disperse the particles, and then cooling the mixture.

[0174] In addition, when the amorphous resin is, for example, a styrene-acrylic resin, the release agent can be incorporated into the toner by previously mixing the release agent with the amorphous resin particles (styrene-acrylic resin particles) that are to be subjected to the aggregation and fusion processes.

[0175] Specifically, a release agent is dissolved in a solution of polymerizable monomers for forming a styrene-acrylic resin. This solution is added to an aqueous medium containing a surfactant, and mechanical energy such as mechanical stirring or ultrasonic energy is applied to finely disperse the solution as described above. A polymerization initiator is then added to carry out polymerization at a desired polymerization temperature, which is called a mini-emulsion polymerization method, to prepare a dispersion of amorphous resin particles containing a release agent.

[0176] <Charge control agent> As the charge control agent, various known compounds can be used.

[0177] The content of the charge control agent in the toner is preferably within a range of 0.1 to 10% by mass, and more preferably within a range of 1 to 5% by mass.

[0178] <External additives> External additives are attached to the surfaces of the toner base particles for the purpose of controlling the fluidity and chargeability.

[0179] As the external additive, conventionally known metal oxide particles can be used, such as silica particles, titanium oxide particles, alumina particles, zirconia particles, zinc oxide particles, chromium oxide particles, cerium oxide particles, antimony oxide particles, tungsten oxide particles, tin oxide particles, tellurium oxide particles, manganese oxide particles, boron oxide particles, etc. These may be used alone or in combination of two or more kinds.

[0180] As for the silica particles, silica particles produced by the sol-gel method can be used. The silica particles produced by the sol-gel method are characterized by a narrow particle size distribution, which is preferable in terms of suppressing the variation in adhesion strength.

[0181] The number-average primary particle size of the silica particles formed by the sol-gel method is preferably within the range of 70 to 150 nm. The silica particles having a number-average primary particle size within this range have a larger particle size than other external additives, and therefore act as a spacer, preventing other external additives with smaller particle sizes from being embedded in the toner base particles when stirred and mixed in the developing machine, and also preventing the toner base particles from fusing together.

[0182] Furthermore, organic particles of homopolymers such as styrene and methyl methacrylate, or copolymers thereof may be used as an external additive.

[0183] The metal oxide particles used as the external additive are preferably those that have been subjected to a hydrophobic surface treatment using a known surface treatment agent such as a coupling agent, etc. As the above surface treatment agent, dimethyldimethoxysilane, hexamethyldisilazane (HMDS), methyltrimethoxysilane, isobutyltrimethoxysilane, decyltrimethoxysilane, etc. are preferred.

[0184] Silicone oil can also be used as the surface treatment agent. Specific examples of silicone oil include organosiloxane oligomers, octamethylcyclotetrasiloxane, or cyclic compounds such as decamethylcyclopentasiloxane, tetramethylcyclotetrasiloxane, and tetravinyltetramethylcyclotetrasiloxane, and linear or branched organosiloxanes. Silicone oils with high reactivity and at least terminal modification, in which modified groups are introduced into the side chain, one terminal, both terminals, one terminal of the side chain, or both terminals of the side chain, may also be used. Examples of the modified group include, but are not limited to, an alkoxy group, a carboxy group, a carbinol group, a higher fatty acid modified group, a phenol group, an epoxy group, a methacryl group, and an amino group. Silicone oils with several modified groups, such as amino / alkoxy modified groups, may also be used.

[0185] Dimethyl silicone oil may be mixed with the modified silicone oil and / or other surface treatment agents, such as silane coupling agents, titanate coupling agents, aluminate coupling agents, various silicone oils, fatty acids, fatty acid metal salts, esters thereof, rosin acid, etc.

[0186] In order to further improve the cleaning property and transferability, a lubricant may be used as an external additive. Examples of the lubricant include metal salts of higher fatty acids such as the following salts of stearic acid with zinc, aluminum, copper, magnesium, calcium, etc., salts of oleic acid with zinc, manganese, iron, copper, magnesium, etc., salts of palmitic acid with zinc, copper, magnesium, etc., salts of linoleic acid with zinc, calcium, etc., and salts of ricinoleic acid with zinc, calcium, etc.

[0187] The total amount of these external additives added is preferably within a range of 0.1 to 10% by mass, and more preferably within a range of 1 to 5% by mass, based on 100 parts by mass of the toner base particles.

[0188] The toner according to the present invention preferably has a core-shell structure including a core particle containing a binder resin and a colorant, and a shell layer covering the surface of the core particle. The shell layer is not limited to one that completely covers the core particle, and the surface of the core particle may be partially exposed. The toner has a core-shell structure, which can provide charging stability and heat-resistant storage stability. The resin constituting the shell layer is not particularly limited, but it is preferable to use an amorphous polyester resin or an amorphous vinyl resin.

[0189] The core-shell structure can be confirmed by observing the cross-sectional structure of the toner using known means such as a transmission electron microscope (TEM) or a scanning probe microscope (SPM).

[0190] [1.5] Toner manufacturing method The toner according to the present invention can be produced by a production method including the following procedures. However, this is merely an example, and the present invention is not limited to the following production example.

[0191] The toner of the present invention is preferably produced by a wet method in an aqueous medium, and can be produced, for example, by an emulsion aggregation method.

[0192] The emulsion aggregation method is a method for producing a toner by mixing an aqueous dispersion of resin particles constituting a binder resin with an aqueous dispersion of particles of other toner constituent components as necessary, slowly aggregating the particles while balancing the repulsive force of the particle surfaces by adjusting the pH and the aggregating force by adding an aggregating agent made of an electrolyte, and causing association while controlling the average particle size and particle size distribution, and at the same time, fusing the fine particles together by heating and stirring to control the shape.

[0193] In the following, as an example of a method for producing a toner, a case in which a crystalline polyester resin and an amorphous resin are used as a binder resin will be described.

[0194] A specific example of such a toner manufacturing method is (1) a colorant particle dispersion preparation step of dispersing a colorant in an aqueous medium to prepare a colorant particle dispersion; (2) a crystalline polyester resin particle dispersion preparation step of dispersing a crystalline polyester resin in an aqueous medium to prepare a crystalline polyester resin particle dispersion; (3) An amorphous resin particle dispersion preparation step in which an amorphous resin (amorphous polyester resin, amorphous vinyl resin) containing toner components such as a release agent and a charge control agent as necessary is dispersed in an aqueous medium to prepare an amorphous resin particle dispersion (amorphous polyester resin particle dispersion, amorphous vinyl resin particle dispersion); (4) an aggregation and fusion step in which the amorphous resin particles, the crystalline polyester resin particles, and the colorant particles are aggregated and fused in an aqueous medium using each of the dispersions obtained in the above (1) to (3) to form aggregated particles; (5) a maturation step in which the aggregated particles are maturated by thermal energy to adjust the shape and prepare a toner base particle dispersion; (6) A cooling step of cooling the toner base particle dispersion; (7) A process of separating the toner base particles from the cooled toner base particle dispersion liquid into a solid-liquid mixture, and filtering and washing the particles to remove surfactants and the like from the surfaces of the toner base particles; (8) A drying step of drying the washed toner base particles; (9) An external additive treatment step of adding an external additive to the dried toner base particles; It consists of:

[0195] In the present invention, the term "aqueous medium" refers to a medium consisting of 50 to 100% by mass of water and 0 to 50% by mass of a water-soluble organic solvent. Examples of the water-soluble organic solvent include methanol, ethanol, isopropanol, butanol, acetone, methyl ethyl ketone, and tetrahydrofuran, and it is preferable to use an alcohol-based organic solvent that does not dissolve the resulting resin.

[0196] (1) Colorant particle dispersion preparation process The colorant particle dispersion can be prepared by dispersing the colorant in an aqueous medium. The colorant is preferably dispersed in an aqueous medium with a surfactant concentration equal to or higher than the critical micelle concentration (CMC) in order to disperse the colorant uniformly. Various known dispersers can be used as the dispersing machine for dispersing the colorant.

[0197] (Surfactant) Examples of the surfactant include anionic surfactants such as alkyl sulfate ester salts, polyoxyethylene (n) alkyl ether sulfate salts, alkylbenzene sulfonates, α-olefin sulfonates, and phosphate esters; amine salt-type surfactants such as alkylamine salts, aminoalcohol fatty acid derivatives, polyamine fatty acid derivatives, and imidazolines; cationic surfactants of quaternary ammonium salt-type surfactants such as alkyltrimethylammonium salts, dialkyldimethylammonium salts, alkyldimethylbenzylammonium salts, pyridinium salts, alkylisoquinolinium salts, and benzethonium chloride; nonionic surfactants such as fatty acid amide derivatives and polyhydric alcohol derivatives; amphoteric surfactants such as alanine, dodecyldi(aminoethyl)glycine, di(octylaminoethyl)glycine, and N-alkyl-N,N-dimethylammonium betaine; and anionic surfactants and cationic surfactants having a fluoroalkyl group can also be used.

[0198] The dispersion diameter of the colorant particles in the colorant particle dispersion liquid prepared in this colorant particle dispersion liquid preparation step is preferably within a range of 10 to 300 nm in volume-based median diameter. The volume-based median diameter of the colorant particles in this colorant particle dispersion liquid is measured with an electrophoretic light scattering photometer "ELS-800 (manufactured by Otsuka Electronics Co., Ltd.)".

[0199] The colorant may be incorporated into the toner by dissolving or dispersing it in advance in a monomer solution for forming the amorphous resin by using a mini-emulsion method in the amorphous resin particle dispersion preparation step described below.

[0200] (2) Crystalline polyester resin particle dispersion preparation process Methods for dispersing crystalline polyester resin in an aqueous medium include the aqueous direct dispersion method, in which the crystalline polyester resin is dispersed in an aqueous medium containing added surfactant by ultrasonic dispersion method or bead mill dispersion method, etc.; the dissolution emulsification / desolvation method, in which the crystalline polyester resin is dissolved in a solvent, dispersed in an aqueous medium to form emulsified particles (oil droplets), and then the solvent is removed, and the phase inversion emulsification method.

[0201] The average particle size of the crystalline polyester resin particles obtained in the crystalline polyester resin particle dispersion preparation step is preferably in the range of, for example, 50 to 500 nm in terms of volume-based median diameter. The volume-based median diameter is measured using "UPA-EX150" (manufactured by Microtrack Bell Co., Ltd.).

[0202] (3) Amorphous resin particle dispersion preparation process When the amorphous resin is an amorphous polyester resin, the amorphous polyester resin particle dispersion liquid can be prepared by dispersing the synthesized amorphous polyester resin in an aqueous medium. The method for dispersing the amorphous polyester resin in an aqueous medium can be the same as the method for dispersing the crystalline polyester resin in an aqueous medium described above.

[0203] When the amorphous resin is an amorphous vinyl resin, a polymerizable monomer for forming the amorphous vinyl resin is added to an aqueous medium containing a surfactant at a concentration equal to or higher than the critical micelle formation concentration (CMC), and a water-soluble polymerization initiator is added at a desired polymerization temperature while stirring to carry out polymerization, thereby preparing an amorphous vinyl resin particle dispersion liquid.

[0204] Similarly, when the amorphous resin is an amorphous vinyl resin, a liquid in which a toner component such as a release agent or a charge control agent is dissolved or dispersed as necessary in a polymerizable monomer for forming the amorphous vinyl resin is added to an aqueous medium containing a surfactant at a critical micelle concentration (CMC) or less, mechanical energy is applied to form droplets, and then a water-soluble radical polymerization initiator is added to proceed with a polymerization reaction in the droplets, thereby preparing an amorphous resin particle dispersion. An oil-soluble polymerization initiator may be contained in the droplets. In such an amorphous resin particle dispersion preparation process, a process of applying mechanical energy to emulsify (form droplets) is essential. Examples of means for applying such mechanical energy include means for applying strong stirring or ultrasonic vibration energy such as a homomixer, ultrasonic wave, or Manton-Gaulin.

[0205] The amorphous resin particles formed in this amorphous resin particle dispersion preparation process can also be made to have a structure of two or more layers made of resins with different compositions. In this case, a method can be adopted in which a polymerization initiator and a polymerizable monomer are added to a dispersion of resin particles prepared by a conventional emulsion polymerization treatment (first stage polymerization), and this system is then polymerized (second stage polymerization, third stage polymerization).

[0206] When a surfactant is used in this step, the surfactant may be, for example, the same as the surfactant described above.

[0207] (Polymerization initiator) As the polymerization initiator to be used, various known polymerization initiators can be used.Specifically, for example, hydrogen peroxide, acetyl peroxide, cumyl peroxide, tert-butyl peroxide, propionyl peroxide, benzoyl peroxide, chlorobenzoyl peroxide, dichlorobenzoyl peroxide, bromomethylbenzoyl peroxide, lauroyl peroxide, ammonium persulfate, sodium persulfate, potassium persulfate, diisopropyl peroxycarbonate, tetralin hydroperoxide, 1-phenyl-2-methylpropyl-1-hydroperoxide, pertriphenylacetic acid-tert-hydroperoxide, performic acid-tert-butyl, peracetic acid-tert- peroxides such as butyl, tert-butyl perbenzoate, tert-butyl perphenylacetate, tert-butyl permethoxyacetate, and tert-butyl per-N-(3-tolyl)palmitate; and azo compounds such as 2,2'-azobis(2-amidinopropane) hydrochloride, 2,2'-azobis(2-amidinopropane) nitrate, 1,1'-azobis(1-methylbutyronitrile-3-sodium sulfonate), 4,4'-azobis-4-cyanovaleric acid, and poly(tetraethylene glycol-2,2'-azobisisobutyrate). Among these, water-soluble polymerization initiators such as ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide, 2,2'-azobis(2-amidinopropane) hydrochloride, 2,2'-azobis(2-amidinopropane) nitrate, 1,1'-azobis(1-methylbutyronitrile-3-sodium sulfonate), and 4,4'-azobis-4-cyanovaleric acid can be preferably used.

[0208] As the polymerization initiator, a redox polymerization initiator such as a combination of persulfate and metabisulfite, or a combination of hydrogen peroxide and ascorbic acid can also be used.

[0209] (Chain transfer agent) In the step of preparing a dispersion liquid of amorphous resin (particularly amorphous vinyl resin), a commonly used chain transfer agent can be used for the purpose of adjusting the molecular weight of the amorphous resin. The chain transfer agent is not particularly limited, and examples thereof include alkyl mercaptan, mercapto fatty acid ester, etc.

[0210] The average particle size of the amorphous resin particles obtained in this amorphous resin particle dispersion preparation step is preferably within a range of, for example, 50 to 500 nm in terms of volume-based median diameter. The volume-based median diameter is measured using "UPA-EX150" (manufactured by Microtrack Bell Co., Ltd.).

[0211] (4) Agglomeration and fusion process In this step, the colorant particles, amorphous resin particles, and crystalline polyester resin particles contained in the dispersion liquid formed in the above step are aggregated and fused in an aqueous medium. In this step, an amorphous resin particle dispersion, a crystalline polyester resin particle dispersion, and a colorant particle dispersion are added to an aqueous medium to aggregate and fuse these particles.

[0212] A specific method for aggregating and fusing the colorant particles, amorphous resin particles, and crystalline polyester resin particles is a method in which an aggregating agent is added to an aqueous medium so as to reach a critical aggregating concentration or higher, and then heating is performed to a temperature that is equal to or higher than the glass transition point of the amorphous resin particles and equal to or higher than the melting peak temperature of the release agent and the crystalline polyester resin, thereby proceeding with salting out of particles such as the colorant particles, amorphous resin particles, and crystalline polyester resin particles and simultaneously proceeding with fusion in parallel, and when the particles have grown to a desired particle size, an aggregation terminator is added to stop the particle growth, and further heating is continued as necessary to control the particle shape.

[0213] In this method, it is preferable to leave the mixture after adding the flocculant for as short a time as possible and quickly heat the mixture to a temperature equal to or higher than the glass transition point of the amorphous resin particles associated with the binder resin. The reason for this is not clear, but it is because there is a concern that depending on the time left after salting out, the particle aggregation state may change, making the particle size distribution unstable, or the surface properties of the fused particles may change. The time until the temperature rise is usually preferably within 30 minutes, more preferably within 10 minutes.

[0214] The heating rate is preferably 1° C. / min or more. Although there is no particular upper limit to the heating rate, it is preferably 15° C. / min or less from the viewpoint of suppressing the generation of coarse particles due to the rapid progress of fusion. Furthermore, after the reaction system reaches a temperature equal to or higher than the glass transition point, it is essential to maintain the temperature of the reaction system for a certain period of time to continue the fusion. This allows the growth and fusion of the toner to proceed effectively, and improves the durability of the toner finally obtained.

[0215] (Flocculant) The flocculant to be used is not particularly limited, but one selected from metal salts is preferably used. Examples of metal salts include monovalent metal salts such as salts of alkali metals such as sodium, potassium, and lithium; divalent metal salts such as calcium, magnesium, manganese, and copper; and trivalent metal salts such as iron and aluminum. Specific examples of metal salts include sodium chloride, potassium chloride, lithium chloride, calcium chloride, magnesium chloride, zinc chloride, copper sulfate, magnesium sulfate, and manganese sulfate. Among these, it is particularly preferable to use divalent metal salts because they can promote flocculation with a small amount and are easy to control the flocculation property. These can be used alone or in combination of two or more.

[0216] When a surfactant is used in this step, the surfactant may be, for example, the same as the surfactant described above.

[0217] (5) Aging process Specifically, this process is a process in which a system containing aggregated particles is heated and stirred, and the heating temperature, stirring speed, and heating time are controlled until the shape of the aggregated particles reaches a desired average circularity, thereby forming toner base particles. In this process, it is preferable to control the shape of the toner base particles by thermal energy (heating).

[0218] (6) Cooling process ~ (8) Drying process The cooling step, filtration step, washing step and drying step can be carried out by adopting various known methods.

[0219] (9) External additive processing process In this external additive treatment step, an external additive is added to and mixed with the dried toner base particles.

[0220] The method of adding the external additive includes a dry method in which a powdered external additive is added to and mixed with dried toner base particles, and a mechanical mixer such as a Henschel mixer or a coffee mill can be used as the mixer.

[0221] [1.6] Toner properties <Average particle size of toner> In the toner of the present invention, the individual toner particles constituting the toner preferably have an average particle size, for example, in the range of 3 to 8 μm, more preferably 5 to 8 μm, in terms of volume-based median diameter.

[0222] When the toner is produced by employing, for example, an emulsion aggregation method described later, this average particle size can be controlled by the concentration of the aggregating agent used, the amount of organic solvent added, the fusion time, the composition of the polymer, etc. When the volume-based median diameter is within the above range, the transfer efficiency is increased, improving the image quality of halftones and the image quality of fine lines, dots, etc.

[0223] The volumetric median diameter of the toner is measured and calculated using a measuring device consisting of a "Multisizer 3" (manufactured by Beckman Coulter) connected to a computer system equipped with the data processing software "Software V3.51."

[0224] Specifically, 0.02 g of the measurement sample (toner) is added to 20 mL of surfactant solution (a surfactant solution prepared by diluting, for example, a neutral detergent containing a surfactant component with pure water 10 times for the purpose of dispersing the toner) and allowed to mix, then ultrasonic dispersion is performed for 1 minute to prepare a toner dispersion, and this toner dispersion is pipetted into a beaker containing an "ISOTON II" (manufactured by Beckman Coulter) in a sample stand until the displayed concentration on the measuring device is 8%. By setting the concentration within this range, reproducible measurement values ​​can be obtained. Then, in the measuring device, the measurement particle count is set to 25,000 particles, the aperture diameter is set to 100 μm, and the measurement range of 2 to 60 μm is divided into 256 parts to calculate the frequency value, and the particle size of the largest 50% of the volume cumulative fraction is taken as the volume-based median diameter.

[0225] <Average circularity of toner> In the toner of the present invention, from the viewpoint of the stability of the charging characteristics and the low-temperature fixing ability, the average circularity of each toner particle constituting the toner is preferably within the range of 0.930 to 1.000, and more preferably within the range of 0.950 to 0.995. By having the average circularity within the above range, the individual toner particles are less likely to be crushed, the contamination of the frictional charging member is suppressed, the charging characteristics of the toner are stabilized, and the image formed has high image quality.

[0226] In the present invention, the average circularity of the toner is measured using "FPIA-3000" (manufactured by Sysmex Corporation).

[0227] Specifically, the sample (toner) is mixed in an aqueous solution containing a surfactant, and dispersed by ultrasonic dispersion treatment for 1 minute. Then, using an "FPIA-3000" (manufactured by Sysmex Corporation), images are taken in HPF (high magnification imaging) mode as the measurement condition, at an appropriate concentration of 3,000 to 10,000 HPF detections. The circularity of each toner particle is calculated according to the following formula (T), and the circularity of each toner particle is added up and divided by the total number of toner particles.

[0228] Formula (T): Circularity = (perimeter of a circle with the same projected area as the particle image) / (perimeter of the projected image of the particle)

[0229] <Softening point of toner> The softening point of the toner is preferably within a range of 80 to 120°C, more preferably within a range of 90 to 110°C, from the viewpoint of obtaining low-temperature fixability for the toner.

[0230] The softening point of the toner is measured by the flow tester described below.

[0231] Specifically, 1.1 g of the sample (toner) was placed in a petri dish in an environment of 20°C and 50% RH, flattened, and left for 12 hours or more. After that, it was pressed at 3820 kg / cm using a molding machine "SSP-10A" (manufactured by Shimadzu Corporation). 2 The molded sample was then extruded from the cylindrical die hole (1 mm diameter x 1 mm) using a piston with a diameter of 1 cm at the end of preheating under the conditions of a load of 196 N (20 kgf), a starting temperature of 60 °C, a preheating time of 300 seconds, and a heating rate of 6 °C / min using a flow tester "CFT-500D" (Shimadzu Corporation). The offset method temperature T was measured using a melting temperature measurement method with an offset value of 5 mm. offset is considered to be the softening point.

[0232] [1.7] Developer The toner of the present invention can be used as a magnetic or non-magnetic one-component developer, but may also be mixed with a carrier and used as a two-component developer.

[0233] As the carrier, for example, magnetic particles made of a conventionally known material such as metals such as iron, ferrite, magnetite, and alloys of these metals with metals such as aluminum and lead can be used, and among these, it is preferable to use ferrite particles. Furthermore, as the carrier, a coated carrier in which the surface of a magnetic particle is coated with a coating agent such as a resin, or a resin dispersion type carrier in which a magnetic fine powder is dispersed in a binder resin may also be used.

[0234] The carrier preferably has a volume average particle size in the range of 15 to 100 μm, and more preferably in the range of 25 to 80 μm.

[0235] [2] Electrophotographic image forming method and electrophotographic image forming apparatus The electrophotographic image forming method of the present invention is an electrophotographic image forming method having at least a step of charging an image carrier, a step of forming an electrostatic image, a step of developing an electrostatic image, a step of transferring a toner image, and a step of fixing a toner image, and is characterized in that the electrophotographic image forming method of the present invention uses at least five colors of toner sets for developing electrostatic images.

[0236] In detail, the method includes a charging step of charging the surface of an image holder, an electrostatic image forming step of forming an electrostatic image on the charged surface of the image holder, a developing step of developing the electrostatic image formed on the surface of the image holder as a toner image using at least five colors of the toner set for developing electrostatic images of the present invention, a transfer step of transferring the toner image formed on the surface of the image holder to the surface of a recording medium, and a fixing step of fixing the toner image transferred to the surface of the recording medium.

[0237] (Electrifying process) In this step, the electrophotographic photoreceptor is charged. The charging method is not particularly limited, and may be a known method such as a charging roller method in which the electrophotographic photoreceptor is charged by a charging roller.

[0238] (Process for forming electrostatic latent images) In this process, an electrostatic latent image is formed on an electrophotographic photoreceptor (electrostatic latent image bearing member).

[0239] The electrophotographic photoreceptor is not particularly limited, but examples thereof include drum-shaped ones made of organic photoreceptors such as polysilane or phthalopolymethine.

[0240] The electrostatic latent image is formed, for example, by uniformly charging the surface of the electrophotographic photoreceptor with a charging means and exposing the surface of the electrophotographic photoreceptor to light in an imagewise manner with an exposure means. The electrostatic latent image is an image formed on the surface of the electrophotographic photoreceptor by such a charging means.

[0241] The charging means and the exposure means are not particularly limited, and those generally used in the electrophotographic system can be used.

[0242] (Developing process) The developing step is a step in which the electrostatic latent image is developed with a toner (generally, a dry developer containing a toner) to form a toner image.

[0243] The toner image is formed, for example, by using a dry developer containing toner, using a developing means including a stirrer that frictionally stirs and charges the toner, and a rotatable magnet roller.

[0244] Specifically, in the developing means, for example, toner and carrier are mixed and stirred, and the toner is charged by friction during this process and held on the surface of a rotating magnet roller to form a magnetic brush. Since the magnet roller is disposed in the vicinity of an electrophotographic photoreceptor, a portion of the toner constituting the magnetic brush formed on the surface of the magnet roller moves to the surface of the electrophotographic photoreceptor by electrical attraction. As a result, the electrostatic latent image is developed by the toner to form a toner image on the surface of the electrophotographic photoreceptor.

[0245] In this case, in the toner set according to the present invention, it is preferable to create software in advance that controls the supply amounts of the silicon phthalocyanine compound-containing toner and the copper phthalocyanine compound-containing toner to an image in such a way that, if the high density region of the cyan image increases, the supply amount of the copper phthalocyanine compound-containing toner is increased, and, if the low density region increases, the supply amount of the silicon phthalocyanine compound-containing toner is increased while taking into consideration the color tone, and incorporate the software in the image processing unit 60 of a full-color high-speed multifunction printer that uses toners of at least five colors, which will be described later, to control the supply amount of the toner while detecting the image density region.

[0246] (Transfer process) In this step, the toner image is transferred onto a recording medium.

[0247] The toner image is transferred onto the recording medium by peeling and charging the toner image onto the recording medium.

[0248] As the transfer means, for example, a corona transfer device using corona discharge, a transfer belt, a transfer roller, or the like can be used.

[0249] The transfer step can be carried out, for example, by using an intermediate transfer member, performing primary transfer of a toner image onto the intermediate transfer member, and then secondary transfer of the toner image onto a recording medium, or by directly transferring a toner image formed on an electrophotographic photosensitive member onto a recording medium.

[0250] (Fixing process) The fixing step according to the present invention includes a step of fixing the unfixed image (toner image) formed by using toner to the recording material transferred thereon by passing the recording material between a heated fixing belt or fixing roller and a pressure member. When the fixing belt or fixing roller used is the fixing member according to the present invention, even if the paper output speed of the image forming apparatus is increased (using an image forming apparatus with a copy speed of 70 cpm or more, so-called Seg. 5 or more), a high fixing separation performance can be exhibited and an effect of preventing image unevenness can be obtained.

[0251] Specific examples of the fixing process include a belt fixing method or a roller fixing method, which is configured with a fixing belt or a fixing roller as a fixing rotor and a pressure roller as a pressure member that is in pressure contact with the fixing belt or the fixing roller so as to form a fixing nip portion.

[0252] (Cleaning process) In this step, the developer that has not been used for image formation or that has not been transferred and remains on the developer carrying member such as the photoreceptor or intermediate transfer member is removed from the developer carrying member.

[0253] The cleaning method is not particularly limited, but may be performed by contacting the tip of the cleaning agent with a cleaning target such as a photoconductor. A method using a blade that is placed in contact with the photoreceptor surface and scrapes the surface is preferred.

[0254] In the electrophotographic image forming method of the present invention, the chromatic or black toner image is finally transferred and formed on a recording medium.

[0255] The recording medium is not particularly limited, and examples thereof include plain paper ranging from thin paper to thick paper, coated printing paper such as high-quality paper, art paper, or coated paper, and commercially available paper such as Japanese paper and postcard paper. Examples of the recording medium include, but are not limited to, resin films such as polypropylene (PP) film, polyethylene terephthalate (PET) film, and triacetyl cellulose (TAC) film; cloth, etc. The color of the recording medium is not particularly limited, and recording media of various colors can be used.

[0256] The electrophotographic image forming apparatus of the present invention is an electrophotographic image forming apparatus including at least an image carrier charging means, an electrostatic image forming means, an electrostatic image developing means, a toner image transferring means, and a toner image fixing means, and is characterized in that it uses at least five colors of the toner set for developing electrostatic images of the present invention.

[0257] In detail, the image carrier includes an image carrier, a charging means for charging the surface of the image carrier, an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier, a developing means for developing the electrostatic image formed on the surface of the image carrier as a toner image using the toner set for developing electrostatic images of the present invention, a transfer means for transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing means for fixing the toner image transferred to the surface of the recording medium.

[0258] The electrophotographic image forming apparatus of the present invention is, for example, a tandem type image forming apparatus in which photoconductor drums 83Y, 83M, 83C1, 83C2, and 83K as photoconductors corresponding to five colors, namely, yellow (Y), magenta (M), cyan (C1: toner containing a silicon phthalocyanine compound / C2: toner containing a copper phthalocyanine compound), and black (Bk), are arranged in series in the running direction of an intermediate transfer body, as shown in FIG.

[0259] As shown in FIG. 1, the electrophotographic image forming apparatus 1 includes a control unit (stored in an image processing unit 60: not shown) consisting of a CPU (Central Processing Unit) and memories (not shown) such as a ROM (Read Only Memory) and a RAM (Random Access Memory), a storage unit (not shown) consisting of a HDD (Hard Disk Drive) and an SSD (Solid State Drive), a network I / F unit (not shown) consisting of a NIC (Network Interface Card) and a modem, a display operation unit 40 consisting of a touch panel or the like, an image reading unit 50 consisting of an ADF (Auto Document Feeder) and a scanner, an image processing unit 60 consisting of a RIP (Raster Image Processor), a conveying unit 70, and an image forming unit 80, and the image forming unit 80 which processes paper conveyed from the conveying unit 70 includes the intermediate transfer body of this embodiment.

[0260] As shown in Fig. 1, the transport section 70 is composed of a paper feeder 71, a transport mechanism 72, a paper discharge device 73, and the like. Paper sheets stored in the paper feeder 71 are sent out one by one from the top, and transported to the image forming section 80 by the transport mechanism 72 equipped with a plurality of transport rollers such as registration rollers. At this time, the registration section equipped with registration rollers corrects the inclination of the fed paper and adjusts the transport timing. Then, the paper sheets on which an image has been formed by the image forming section 80 are discharged to a paper discharge tray outside the machine by the paper discharge device 73 equipped with paper discharge rollers.

[0261] As shown in FIG. 1, the image forming unit 80 is composed of an exposure device 81 (81Y, 81M, 81C1, 81C2, 81K), a development device 82 (82Y, 82M, 82C1, 82C2, 82K), a photoconductor drum 83 (83Y, 83M, 83C1, 83C2, 83K), a charging device 84 (84Y, 84M, 84C, 84K), a cleaning device 85 (85Y, 85M, 85C1, 85C285K), a primary transfer roller 86 (86Y, 86M, 86C1, 86C2, 86K), an intermediate transfer unit 87, a fixing device 88, and the like, which are provided corresponding to different color components Y, M, C1, C2, and K. Below, each element will be outlined. In the following description, reference characters excluding Y, M, C, and K will be used as necessary.

[0262] The photoconductor drums 83 for the respective color components Y, M, C, and K are image carriers in which an organic photoconductor layer (OPC) with an overcoat layer as a protective layer is formed on the outer circumferential surface of a cylindrical metal substrate made of aluminum. The photoconductor drums 83 are grounded and rotate counterclockwise in FIG. 1, driven by the intermediate transfer body.

[0263] The charging device 84 for each color component Y, M, C1, C2, and K is of the Scorotron type and is disposed adjacent to the corresponding photosensitive drum 83 with its longitudinal direction aligned with the rotational axis of the photosensitive drum 83. A uniform potential is applied to the surface of the photosensitive drum 83 by corona discharge of the same polarity as the toner.

[0264] The exposure device 81 for each color component Y, M, C1, C2, and K scans parallel to the rotation axis of the photosensitive drum 83, for example by a polygon mirror, and forms an electrostatic latent image on the uniformly charged surface of the corresponding photosensitive drum 83 by image exposure based on image data.

[0265] The developing devices 82 for each color component Y, M, C1, C2, and K contain a two-component developer consisting of small particle size toner of the corresponding color component and a magnetic material, and transport the toner to the surface of the photosensitive drum 83, thereby visualizing the electrostatic latent image carried on the photosensitive drum 83 with the toner.

[0266] The primary transfer rollers 86 for each color component Y, M, C1, C2, and K press the intermediate transfer body of this embodiment against the photosensitive drum 83, and sequentially superimpose the toner images of each color formed on the corresponding photosensitive drum 83 onto the intermediate transfer body.

[0267] The cleaning device 85 for each color component Y, M, C1, C2, and K collects residual toner remaining on the corresponding photoconductor drum 83 after the primary transfer. In addition, a lubricant application mechanism (not shown) is provided adjacent to the cleaning device 85 on the downstream side in the rotation direction of the photoconductor drum 83, and applies a lubricant to the photosensitive surface of the corresponding photoconductor drum 83.

[0268] The intermediate transfer unit 87 includes an endless intermediate transfer body 87a, a support roller 87b, a secondary transfer roller 87c, an intermediate transfer cleaning section 87d, and the like, and is configured by stretching the intermediate transfer body 87a over the multiple support rollers 87b. When the intermediate transfer body 87a, to which the toner images of each color are primarily transferred by the primary transfer rollers 86Y, 86M, 86C1, 86C2, and 86K, is pressed against a sheet by the secondary transfer roller 87c, the toner image is secondarily transferred to the sheet by an electric field acting on the toner based on the transfer voltage between the intermediate transfer body 87a and the secondary transfer roller 87c, and the sheet is sent to the fixing device 88. The intermediate transfer cleaning section 87d has a belt cleaning blade that is in sliding contact with the surface of the intermediate transfer body 87a. The residual toner remaining on the surface of the intermediate transfer body 87a after the secondary transfer is scraped off and removed by the belt cleaning blade.

[0269] The fixing device 88 includes a heating roller 88a as a heat source, a fixing roller 88b, a fixing belt 88c and a pressure roller 88d that are stretched over the heating roller 88a and the pressure roller 88d is in pressure contact with the fixing roller 88b via the fixing belt 88c, and the pressure contact portion forms a nip portion. The fixing belt 88c heated by the heating roller 88a and each roller apply heat and pressure to the paper passing through the nip portion, thereby fixing the unfixed toner image formed on the paper.

[0270] Then, the paper on which the toner image has been fixed by the fixing device 88 is discharged onto a paper discharge tray outside the apparatus by a paper discharge device 73 equipped with a paper discharge roller.

[0271] FIG. 1 shows an example of the image forming apparatus 1 of the present invention, and the structure and configuration thereof can be appropriately changed. EXAMPLES

[0272] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, the terms "parts" and "%" are used, but they represent "parts by mass" or "% by mass" unless otherwise specified.

[0273] First, the methods for measuring various physical properties used in the examples will be described.

[0274] [Method of measuring weight average molecular weight (Mw) and number average molecular weight (Mn)] The Mw and Mn of the resin are determined by the following method. Using an apparatus "HLC-8320GPC" (manufactured by Tosoh Corporation) and a column "TSKguardcolumn + TSKgelSuperHZ-M triple series" (manufactured by Tosoh Corporation), tetrahydrofuran (THF) is passed as a carrier solvent at a flow rate of 0.2 mL / min while maintaining the column temperature at 40°C, and the measurement sample (amorphous resin (A)) is dissolved in THF to a concentration of 1 mg / mL under dissolution conditions of processing for 5 minutes using an ultrasonic disperser at room temperature, and then processed with a membrane filter with a pore size of 0.2 μm to obtain a sample solution, and 10 μL of this sample solution is injected into the apparatus together with the above carrier solvent and detected using a refractive index detector (RI detector). The molecular weight distribution of the measurement sample is calculated using a calibration curve measured using 10 monodisperse polystyrene standard particles.

[0275] [Method of measuring Tg] The glass transition point of the resin is measured by the method (DSC method) specified in ASTM (American Society for Testing and Materials) D3418-82. That is, 4.5 mg of the measurement sample (amorphous resin) is precisely weighed to two decimal places, sealed in an aluminum pan, and set in the sample holder of a differential scanning calorimeter "DSC8500" (manufactured by PerkinElmer). An empty aluminum pan is used as a reference, and temperature control is performed with a measurement temperature of -10 to 120°C, a heating rate of 10°C / min, and a cooling rate of 10°C / min, with heating-cooling-heating, and analysis is performed based on the data from the second heating. The value of the intersection between the extension line of the baseline before the rise of the first endothermic peak and the tangent line showing the maximum slope from the rising part of the first endothermic peak to the peak apex is taken as the glass transition temperature.

[0276] [Acid value measurement method] The acid value is the mass of potassium hydroxide (KOH) required to neutralize the acid contained in 1 g of a sample, expressed in mg. The acid value of a resin is measured according to the following procedure in accordance with JIS K0070-1992.

[0277] (Preparation of reagents) Dissolve 1.0 g of phenolphthalein in 90 mL of ethyl alcohol (95% by volume), add ion-exchanged water to make 100 mL, and prepare a phenolphthalein solution. Dissolve 7 g of JIS special grade potassium hydroxide in 5 mL of ion-exchanged water, and add ethyl alcohol (95% by volume) to make 1 liter. Place in an alkali-resistant container to avoid contact with carbon dioxide, leave for 3 days, then filter to prepare a potassium hydroxide solution. Standardization follows the description of JIS K0070-1992.

[0278] (Actual test) Weigh out 2.0 g of the crushed sample into a 200 mL Erlenmeyer flask, add 100 mL of a toluene / ethanol (toluene:ethanol volume ratio 2:1) mixture, and dissolve for 5 hours. Next, add a few drops of the prepared phenolphthalein solution as an indicator, and titrate with the prepared potassium hydroxide solution. The end point of the titration is when the indicator remains a pale red color for about 30 seconds.

[0279] (Blank test) The same procedure as in the main test described above is carried out, except that no sample is used (i.e., only a mixed solution of toluene / ethanol (toluene:ethanol in a volume ratio of 2:1) is used).

[0280] The titration results of the main test and the blank test are substituted into the following formula (1) to calculate the acid value.

[0281] Formula (1) A=[(BC)×f×5.6] / S A: Acid value (mgKOH / g) B: Amount of potassium hydroxide solution added during blank test (mL) C: Amount of potassium hydroxide solution added during this test (mL) f: Factor of 0.1 mol / L potassium hydroxide ethanol solution S: mass of sample (g)

[0282] [Method of measuring Tm] The melting point (Tm) of the crystalline polyester resin is the temperature at the top of the endothermic peak, and can be measured by DSC using a Diamond DSC (manufactured by PerkinElmer).

[0283] Specifically, the sample is sealed in an aluminum pan KIT NO. B0143013 and set in the sample holder of a thermal analysis device Diamond DSC (manufactured by PerkinElmer), and the temperature is changed in the order of heating, cooling, and heating. In the first heating, the temperature is raised from room temperature (25°C), and in the second heating, the temperature is raised from 0°C at a heating rate of 10°C / min to 150°C, and held at 150°C for 5 minutes. In the cooling, the temperature is lowered from 150°C to 0°C at a heating rate of 10°C / min, and the temperature is held at 0°C for 5 minutes. The temperature of the peak top of the endothermic peak in the endothermic curve obtained in the second heating is measured as the melting point.

[0284] Example 1 <Preparation of Colorant Dispersion> [Preparation of cyan colorant particle dispersion [Cy]] (Preparation of colorant dispersion (water-based dispersion of cyan colorant particles, Cy1) used in toner production) 13 parts by mass of sodium n-dodecyl sulfate was added to 77 parts by mass of ion-exchanged water, and dissolved and stirred to prepare a surfactant aqueous solution. 10 parts by mass of silicon phthalocyanine example compound (I-1) was gradually added to this surfactant aqueous solution as a colorant for cyan toner. After the addition was completed, a dispersion process was performed using an "SC Mill" (manufactured by Nippon Coke & Engineering Co., Ltd.) with zirconia beads (φ0.3 mm) set to a filling rate of 75%, to prepare an aqueous dispersion of cyan colorant particles Cy1. The median diameter d50 of the aqueous dispersion of cyan colorant particles Cy1 obtained was measured using a microtrack particle size distribution analyzer "UPA-150" (manufactured by Nikkiso Co., Ltd.), and was found to be 120 nm.

[0285] (Preparation of colorant dispersion (water-based dispersion of cyan colorant particles, Cy2) used in toner production) An aqueous dispersion of cyan colorant particles Cy2 was prepared in the same manner as in the preparation of the aqueous dispersion of cyan colorant particles Cy1, except that the silicon phthalocyanine example compound (I-3) was used instead of the silicon phthalocyanine example compound (I-1).

[0286] (Preparation of colorant dispersion (water-based dispersion of cyan colorant particles, Cy3) used in toner production) An aqueous dispersion of cyan colorant particles Cy3 was prepared in the same manner as in the preparation of the aqueous dispersion of cyan colorant particles Cy1, except that the silicon phthalocyanine example compound (I-10) was used instead of the silicon phthalocyanine example compound (I-1).

[0287] (Preparation of colorant dispersion liquid (cyan colorant particle dispersion liquid Cy4) used in toner production) 13 parts by mass of sodium n-dodecyl sulfate was added to 77 parts by mass of ion-exchanged water, and dissolved and stirred to prepare a surfactant aqueous solution. 10 parts by mass of a copper phthalocyanine compound (CI Pigment Blue 15:3) was gradually added to this surfactant aqueous solution as a colorant for cyan toner. After the addition was completed, a dispersion process was performed using an "SC Mill" (manufactured by Nippon Coke & Engineering Co., Ltd.) with zirconia beads (φ0.3 mm) set to a filling rate of 75%, to prepare an aqueous dispersion of cyan colorant particles Cy4. The median diameter d50 of the aqueous dispersion of cyan colorant particles Cy4 obtained was measured using a microtrack particle size distribution analyzer "UPA-150" (manufactured by Nikkiso Co., Ltd.) and was found to be 156 nm.

[0288] (Preparation of colorant dispersion (water-based dispersion of cyan colorant particles, Cy5) used in toner production) An aqueous dispersion of cyan colorant particles, Cy5, was prepared in the same manner as in the preparation of the aqueous dispersion of cyan colorant particles, Cy4, except that a copper phthalocyanine compound (CI Pigment Blue 60) was used instead of the copper phthalocyanine compound (CI Pigment Blue 15:3).

[0289] <Preparation of resin particles> [Synthesis of amorphous vinyl resin V1]

[0290] (First stage polymerization) A solution of 8 g of sodium dodecyl sulfate dissolved in 3 L of ion-exchanged water was charged into a 5 L reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device, and the internal temperature was raised to 80°C while stirring at a stirring speed of 230 rpm under a nitrogen stream. After that, a solution of 10 g of potassium persulfate dissolved in 200 g of ion-exchanged water was added, and the liquid temperature was again raised to 80°C.

[0291] A monomer mixture liquid prepared by mixing the following components in the following amounts was added dropwise to the obtained solution over a period of 1 hour, and then polymerization was carried out by heating and stirring at 80°C for 2 hours to prepare resin microparticle dispersion X1 in which resin microparticles x1 were dispersed.

[0292] Styrene 480g n-Butyl acrylate 250g Methacrylic acid 68g

[0293] (Second stage polymerization) A solution of 7 g of sodium polyoxyethylene (2) dodecyl ether sulfate dissolved in 1,460 mL of ion-exchanged water was placed in a 5 L reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device, and heated to 88°C.

[0294] To the obtained solution, resin microparticle dispersion X1 was added in an amount equivalent to 80 g of resin microparticles x1, and a monomer solution at 80°C containing the following components in the following amounts was added to the above solution. The mixture was mixed and dispersed for 1 hour using a mechanical disperser "CREARMIX" (manufactured by M-Technique Co., Ltd., "CREARMIX" is a registered trademark of the company) with a circulation path to prepare a dispersion containing emulsified particles (oil droplets).

[0295] 245g styrene n-Butyl acrylate 95g 35g methacrylic acid n-Octyl-3-mercaptopropionate 4.0g Next, an initiator solution in which 6 g of potassium persulfate was dissolved in 200 mL of ion-exchanged water was added to the obtained dispersion, and the system was heated and stirred at 82°C for 1 hour to carry out polymerization, thereby preparing resin microparticle dispersion X2 in which resin microparticles x2 were dispersed.

[0296] (Third stage polymerization) A solution of 11 g of potassium persulfate dissolved in 400 mL of ion-exchanged water was added to the resin particle dispersion X2, and a monomer composition containing the following components in the following amounts was added dropwise to the solution over 1 hour at a temperature of 82°C. After the dropwise addition, polymerization was carried out by heating and stirring for 2 hours. The resulting dispersion was then cooled to 28°C. In this way, amorphous vinyl resin V1, which is an amorphous vinyl resin, was prepared.

[0297] Styrene 405g n-Butyl acrylate 160g Methacrylic acid 33g n-Octyl-3-mercaptopropionate 10g The dispersion of the amorphous vinyl resin V1 was diluted with ion-exchanged water to a concentration of 30% by mass of the amorphous vinyl resin V1 to obtain an aqueous dispersion VD1. The volume-based median diameter D50z of the resin particles in the aqueous dispersion VD1 was measured to be 215 nm. The weight-average molecular weight Mw of the amorphous vinyl resin V1 was measured to be 30,800.

[0298] [Synthesis of amorphous polyester resin A1] The following components were charged in the following amounts into a reaction vessel equipped with a stirrer, nitrogen inlet tube, temperature sensor, and distillation column. "BPA-PO" stands for 2,2-bis(4-hydroxyphenyl)propane propylene oxide 2-mol adduct, and "BPO-EO" stands for 2,2-bis(4-hydroxyphenyl)propane ethylene oxide 2-mol adduct. Additionally, fumaric acid and terephthalic acid are polycarboxylic acids, and BPA-PO and BPO-EO are polyhydric alcohols.

[0299] Fumaric acid (FA) 1.8 parts by mass Terephthalic acid (TA) 29.2 parts by mass BPA-PO 58.2 parts by mass BPO-EO 6.7 parts by mass

[0300] The temperature of the obtained mixture was raised to 190°C over 1 hour, and after confirming that the mixture was uniformly stirred, dibutyltin oxide was added as a catalyst in an amount of 0.006% by mass relative to the total amount of polyvalent carboxylic acid, and the temperature of the mixture was raised from the same temperature to 240°C over 6 hours while distilling off the water produced. When the temperature reached 240°C, 1.6 parts by mass of trimellitic acid was added to the mixture, and the dehydration condensation reaction was continued while maintaining the temperature at 240°C until the acid value of the product reached 21 mgKOH / g, thereby performing a polymerization reaction to obtain amorphous polyester resin A1, which is an amorphous polyester. The number average molecular weight (Mn) of the obtained amorphous polyester resin A1 was 3600, and the glass transition point (Tg) was 62°C. The acid value, Mn and Tg of the amorphous polyester resin A1 were measured as described above.

[0301] [Preparation of Aqueous Dispersion B1 of Amorphous Polyester Fine Particles] 240 parts by mass of methyl ethyl ketone and 60 parts by mass of isopropyl alcohol (IPA) were added to a reaction vessel equipped with an anchor blade for stirring power, and nitrogen was sent into the reaction vessel to replace the air in the reaction vessel with nitrogen. Next, while the mixed liquid in the reaction vessel was heated to 60°C using an oil bath device, 300 parts by mass of amorphous polyester resin A1 was slowly added to the mixed liquid and dissolved while stirring. Next, 20 parts by mass of 10% ammonia water was added to the resulting mixed liquid, and 1500 parts by mass of deionized water was added to the resulting mixed liquid while stirring using a metering pump. It was confirmed that emulsification had occurred because the resulting mixed liquid was milky white and the stirring viscosity was reduced.

[0302] The obtained emulsion was then pumped up by a pressure difference based on centrifugal force and transferred to a separable flask equipped with a stirring blade that forms a wetted wall on the wall surface of the reaction vessel, a reflux device, and a pressure reduction device using a vacuum pump. The wall temperature inside the reaction vessel was set to 58°C, and the solvent and dispersion medium in the emulsion were distilled off while continuing to stir under reduced pressure conditions. The end point of the distillation was the point at which the obtained dispersion reached 1,000 parts by mass. The pressure inside the reaction vessel was then set to normal pressure, and the dispersion was cooled to room temperature while stirring to obtain an aqueous dispersion B1 of fine particles of amorphous polyester resin A1 with a solid content of 30% by mass.

[0303] The volume-based median diameter (D50v) of the resin fine particles dispersed in the aqueous dispersion B1 was 162 nm.

[0304] [Synthesis of crystalline polyester resin C1] The following components were charged in the amounts shown below into a reaction vessel equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column. Sebacic acid is a polycarboxylic acid.

[0305] Sebacic acid (SA) 205 parts by weight Ethylene glycol 61 parts by weight The temperature of the mixture was increased to 190°C over 1 hour, and after confirming that the mixture was uniformly stirred, Ti(OBu)4 was added as a catalyst to the reaction vessel in an amount of 0.006 mass% based on the total amount of polycarboxylic acid. The temperature of the mixture was then increased from the same temperature to 240°C over 6 hours while distilling off the water produced. The dehydration condensation reaction was continued while maintaining the temperature at 240°C until the acid value of the product reached 20 mgKOH / g, thereby carrying out a polymerization reaction, thereby obtaining a crystalline polyester resin C1.

[0306] [Preparation of Aqueous Dispersion D1 of Crystalline Polyester Fine Particles] 300 parts by mass of methyl ethyl ketone was added to a reaction vessel equipped with an anchor blade for stirring power, and nitrogen was sent into the reaction vessel to replace the air in the reaction vessel with nitrogen. Next, while the methyl ethyl ketone in the reaction vessel was heated to 70°C using an oil bath device, 300 parts by mass of crystalline polyester resin C1 was slowly added to the mixture and dissolved while stirring. Next, 20 parts by mass of 10% ammonia water was added to the resulting mixture, and 1500 parts by mass of deionized water was added to the resulting mixture using a metering pump while stirring. It was confirmed that emulsification had occurred because the resulting mixture was milky white and the stirring viscosity was reduced.

[0307] The resulting emulsion was then pumped up by a pressure difference based on centrifugal force and transferred to a separable flask equipped with a stirring blade that forms a wetted wall on the wall surface of the reaction vessel, a reflux device, and a pressure reduction device using a vacuum pump. The wall temperature inside the reaction vessel was set to 58°C, and the solvent and dispersion medium in the emulsion were distilled off while continuing to stir under reduced pressure conditions. The end point of the distillation was the point at which the resulting dispersion reached 1,000 parts by mass. The pressure inside the reaction vessel was then set to normal pressure, and the dispersion was cooled to room temperature while stirring to obtain an aqueous dispersion D1 of fine particles of crystalline polyester resin C1 with a solid content of 30% by mass.

[0308] [Preparation of aqueous dispersion W1 of release agent particles] 50 parts by mass of "Nissan Electol WEP-3" (manufactured by NOF Corporation, melting point (Tm): 73°C, "Nissan Electol" and "WEP" are both registered trademarks of the company), 5 parts by mass of sodium polyoxyethylene-2-dodecyl ether sulfate, and 195 parts by mass of ion-exchanged water were mixed, heated to 90°C, and thoroughly dispersed using a homogenizer "Ultra Turrax T50" (manufactured by IKA Corporation), and then dispersed using a pressure discharge type Gaulin homogenizer to prepare aqueous dispersion W1, which is an aqueous dispersion of release agent particles. The volume-based median diameter D50v of the release agent particles in the aqueous dispersion W1 was 170 nm. "Nissan Electol WEP-3" is a refined product whose main component is behenyl behenate (BB).

[0309] <Production of Cyan Toner 1> A reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube and a nitrogen introducing device was charged with 2333 parts by mass of an aqueous dispersion VD1 of amorphous vinyl resin microparticles (700 parts by mass in terms of solid content), a colorant microparticle dispersion Cy1 such that the amount in the toner was 3.3% by mass, 375 parts by mass of an aqueous dispersion W1 of release agent microparticles (75 parts by mass in terms of solid content), and 942 parts by mass of ion-exchanged water, and while stirring, a 5 mol / L aqueous sodium hydroxide solution was added to the resulting mixture to adjust the pH of the mixture to 10 (20°C).

[0310] Next, an aqueous solution in which 160 parts by mass of magnesium chloride was dissolved in 160 parts by mass of ion-exchanged water was added to the above mixture at a rate of 10 parts by mass / min. After leaving it for 5 minutes, the temperature of the resulting mixture was started to rise, and the temperature was raised to 80°C over 60 minutes. After the temperature was raised, 267 parts by mass of aqueous dispersion D1 of crystalline polyester resin particles (80 parts by mass in solid content) was added to the mixture left for 5 minutes at a rate of 25 parts by mass / min. After leaving it for 15 minutes, the aggregation reaction was started. After the start of this aggregation reaction, sampling was performed periodically, and the median diameter D50v of the volume-based aggregated particles generated was measured using a particle size distribution measuring device "Coulter Multisizer 3" (manufactured by Beckman Coulter, Inc.), and the stirring was continued until D50v became 6.3 μm while reducing the stirring speed as necessary, and the aggregation reaction was continued.

[0311] Then, when D50v reached 6.3 μm, the stirring speed was increased again, and 333 parts by mass of aqueous dispersion B1 of amorphous polyester resin particles (100 parts by mass in terms of solid content) was added at a rate of 25 parts by mass / min. After periodically sampling and confirming that the supernatant of the centrifugation was transparent, an aqueous solution in which 300 parts by mass of sodium chloride was dissolved in 1200 parts by mass of ion-exchanged water was added to the above mixture, the temperature of the mixture was kept at 85° C., and stirring was continued. When the average circularity of the particles in the mixture reached 0.952 as measured by a flow-type particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation, "FPIA" is a registered trademark of the company), the above mixture was cooled to 30° C. at a condition of 6° C. / min to stop the aggregation reaction, and a dispersion of toner particles was obtained. The particle size (D50v) of the toner particles after cooling was 6.3 μm, and the average circularity was 0.952.

[0312] The obtained dispersion of toner particles was subjected to solid-liquid separation using a basket-type centrifuge "MARK III Model No. 60×40" (manufactured by Matsumoto Machinery Manufacturing Co., Ltd.) to obtain a wet cake. The obtained wet cake was repeatedly washed and separated into solid and liquid until the electrical conductivity of the filtrate reached 15 μS / cm using the basket-type centrifuge, and the washed cake was gradually fed to a "Flash Jet Dryer" (manufactured by Seishin Enterprise Co., Ltd.) and dried until the moisture content was about 2.0% by mass by blowing air at a temperature of 40° C. and a humidity of 20% RH, and then cooled to 24° C. The cake was then transferred to a "Vibration Fluidized Bed Device" (manufactured by Chuo Kakoki Co., Ltd.) and dried for 2 hours at a temperature of 40° C. to obtain toner base particles 1X containing a silicon phthalocyanine compound and having a moisture content of 0.5% or less.

[0313] To the obtained toner base particles 1X, 1% by mass of hydrophobic silica and 1.2% by mass of hydrophobic titanium oxide were added, and the mixture was mixed for 20 minutes at a rotor speed of 24 mm / sec using a "Henschel Mixer" (manufactured by Nippon Coke and Engineering Co., Ltd.). After that, an external additive treatment was performed to remove coarse particles using a 400 mesh sieve, thereby producing toner particles 1.

[0314] Further, a ferrite carrier coated with a silicone resin and having a volume average particle size of 60 μm was added to and mixed with the toner particles 1 so that the toner particle concentration became 6 mass %. In this manner, cyan toner 1, which is a two-component developer, was produced.

[0315] <Production of Cyan Toner 2> Cyan toner 2 was prepared in the same manner as in the preparation of cyan toner 1, except that the aqueous dispersion of cyan colorant particles Cy2 was used instead of the aqueous dispersion of cyan colorant particles Cy1.

[0316] <Production of Cyan Toner 3> Cyan toner 3 was prepared in the same manner as in the preparation of cyan toner 1, except that the aqueous dispersion of cyan colorant particles Cy3 was used instead of the aqueous dispersion of cyan colorant particles Cy1.

[0317] <Production of Cyan Toner 4> Cyan toner 4 was prepared in the same manner as in the preparation of cyan toner 1, except that the aqueous dispersion of cyan colorant particles Cy4 was used instead of the aqueous dispersion of cyan colorant particles Cy1.

[0318] <Production of Cyan Toner 5> Cyan toner 5 was prepared in the same manner as in the preparation of cyan toner 1, except that the aqueous dispersion of cyan colorant particles Cy2 was used instead of the aqueous dispersion of cyan colorant particles Cy1.

[0319] <<Preparation of other colorant dispersions for use in toner sets>> [Preparation of aqueous dispersion Y1 of yellow colorant particles] 95 parts by mass of sodium n-dodecyl sulfate was added to 1600 parts by mass of ion-exchanged water. 250 parts by mass of CI Pigment Yellow 74 was gradually added to the solution while stirring, and then a dispersion process was performed using a stirring device "Clearmix" (manufactured by M Technique Co., Ltd.) to prepare an aqueous dispersion of yellow colorant particles (Y1). The volume-based median diameter of the colorant particles in the aqueous dispersion of yellow colorant particles (Y1) was 126 nm.

[0320] [Preparation of aqueous dispersion M1 of magenta colorant particles] 95 parts by mass of sodium n-dodecyl sulfate was added to 1600 parts by mass of ion-exchanged water. 250 parts by mass of CI Pigment Red 122 was gradually added to the solution while stirring, and then a dispersion process was performed using a stirring device "Clearmix" (manufactured by M Technique Co., Ltd.) to prepare an aqueous dispersion of magenta colorant particles (M1). The volume-based median diameter of the colorant particles in the aqueous dispersion of magenta colorant particles M1 was 5 nm.

[0321] [Preparation of aqueous dispersion M2 of magenta colorant particles; high chroma magenta] Dissolve 63 parts by mass of sodium n-dodecyl sulfate in 880 parts by mass of ion-exchanged water with stirring. To this surfactant aqueous solution, 80 parts by mass of the following complex compound 1 and 100 parts by mass of quinacridone (CI Pigment Red 122) were gradually added, and then a dispersion treatment was performed using "Clearmix (registered trademark) W Motion CLM-0.8" (manufactured by M Technique Co., Ltd.) to prepare an aqueous dispersion M2 of magenta colorant particles with a solid content of 16% by mass in which the complex compound 1 and quinacridone particles were dispersed.

[0322] [ka]

[0323] [Preparation of aqueous dispersion Bk1 of black colorant particles] 90 parts by mass of sodium n-dodecyl sulfate was added to 1600 parts by mass of ion-exchanged water. While stirring this solution, 320 parts by mass of carbon black "Regal 330R" (manufactured by Cabot Corporation) was gradually added to the solution, and then the solution was dispersed using a stirring device "Clearmix" (manufactured by M-Technique Co., Ltd.) to prepare an aqueous dispersion of black colorant particles (Bk-1). The volume-based median diameter of the colorant fine particles in the aqueous dispersion of black colorant particles Bk1 was 110 nm.

[0324] <Production of Yellow Toner 1> Yellow toner 1 was prepared in the same manner as in the preparation of cyan toner 1, except that the aqueous dispersion liquid Cy1 of cyan colorant particles was replaced with the aqueous dispersion liquid Y1 of yellow colorant particles.

[0325] <Manufacture of Magenta Toner 1> Magenta toner 1 was prepared in the same manner as in the preparation of cyan toner 1, except that the aqueous dispersion liquid M1 of magenta colorant particles was used instead of the aqueous dispersion liquid Cy1 of cyan colorant particles.

[0326] <Production of Magenta Toner 2: High Chroma Magenta Toner> Magenta toner 2 was prepared in the same manner as in the preparation of cyan toner 1, except that the aqueous dispersion liquid Cy1 of cyan colorant particles was replaced with the aqueous dispersion liquid M2 of magenta colorant particles.

[0327] <Production of Black Toner 1> Black toner 1 was prepared in the same manner as in the preparation of cyan toner 1, except that the aqueous dispersion liquid Cy1 of cyan colorant particles was replaced with the aqueous dispersion liquid Bk1 of black colorant particles.

[0328] <<Toner set composition>> A toner set was prepared using the toner prepared above in the configuration shown in Table I below.

[0329] [Table 1]

[0330] <Hue angle and saturation> Using a commercially available full-color high-speed multifunction printer "bizhub PRO (registered trademark) C8000 (manufactured by Konica Minolta)," in an environment of 20°C temperature and 50% RH, the amount of toner adhesion on the paper was adjusted to 3.4 gsm cyan toner, and an image (a solid image patch measuring 2 cm long x 2 cm wide) was fixed and the color gamut was evaluated.

[0331] The transfer paper used for the evaluation was "POD gloss coated paper 128g / m 2 (manufactured by Oji Paper Co., Ltd.) was used. The fixing temperature was set at a temperature of +10°C from the minimum temperature.

[0332] When calculating the hue angle and saturation, * a * b * The "L color system" is used. * The axis direction indicates brightness, and * The axis direction represents the hue in the red-green direction, and b * The axis direction indicates the hue from yellow to blue. * and b * The measurements were taken using a spectrophotometer "Gretag Macbeth Spectrolino" (manufactured by Gretag Macbeth) under the following conditions: a D50 light source, a measurement wavelength range of 380 to 730 nm at 10 nm intervals, a viewing angle of 2°, a UV-cut filter, and a dedicated white tile for reference alignment.

[0333] In addition, the hue angle h and chroma C * was calculated and evaluated according to the following formula:

[0334] h = tan-1(b * / a * ) C * =[(a * ) 2 +(b * ) 2 ] 1 / 2 As a result of the above evaluation, the hue angle of cyan toners 1 to 3 was 220°, and the chroma was C * Cyan toners 4 and 5 have a hue angle of 235° and a chroma of C * The toner developed a cyan color at 65°.

[0335] "evaluation" The prepared toner set was used to carry out the following evaluations.

[0336] [Image clarity and smoothness of gradation] Using a device modified to be able to set the printing speed to 620 mm / sec (approximately 130 sheets / min) from the five-color modified full-color high-speed multifunction printer "bizhub PRO (registered trademark) C8000 (manufactured by Konica Minolta Business Technologies, Inc.)" shown in Fig. 1, two typical landscape paintings for each season and CMYK originals shown in Fig. 2 were output in an environment of 20°C temperature and 50% RH. In this case, in Examples 1 to 7 according to the present invention, the supply amount of the silicon phthalocyanine compound-containing toner and the copper phthalocyanine compound-containing toner to the cyan image was increased when the high density region of the cyan image increased, and increased when the low density region increased, taking into consideration the color tone, and so on. Software was created to control the supply amount according to the density region of the image in advance, and was incorporated into the image processing unit 60 of the five-color modified full-color high-speed multifunction printer, and the supply amount was controlled while detecting the image density region.

[0337] The obtained images were evaluated by 79 people on a 10-point scale for image clarity and smoothness of gradation, and the average values ​​were ranked as follows. The transfer paper used for the evaluation was "POD gloss coated paper 128g / m 2 (Oji Paper Co., Ltd.) was used. The higher the value, the clearer the image and the smoother the gradation.

[0338] (Rank rating) ◎: 9.0 or higher ○: 7.0 or more and less than 9.0 △: 5.0 or more and less than 7.0 ×: Less than 5.0

[0339] [Table 2]

[0340] From the results in Table II, it was confirmed that the toner set of the present invention is a toner set superior in image clarity and smoothness of gradation to the toner set of the comparative example. In particular, it was found from Examples 4 to 7 that the image clarity and smoothness of gradation of each landscape and CMYK original were further improved by using a high chroma magenta toner in the toner set. [Explanation of symbols]

[0341] 1. Electrophotographic image forming apparatus 40 Display operation section 50 Image reading unit 60 Image Processing Unit 70 Conveyor 71 Paper feeder 72 Transport mechanism 73 Paper ejection device 80 Image forming section 81, 81Y, 81M, 81C1, 81C2, 81K Exposure equipment 82, 82Y, 82M, 82C1, 82C2, 82K Developing Unit 83, 83Y, 83M, 83C1, 83C2, 83K Photoconductor Drum 84, 84Y, 84M, 84C1, 84C2, 84K Charging device 85, 85Y, 85M, 85C1, 85C2, 85K Cleaning Device 86, 86Y, 86M, 86C1, 86C2, 86K Primary transfer roller 87 Intermediate transfer unit 87a Intermediate transfer body 87b Support roller 87c Secondary transfer roller 87d Intermediate transfer cleaning unit 88 Fixing device 88a Heating roller 88b Fuser roller 88c Fuser belt 88d Pressure roller

Claims

1. A toner set for developing an electrostatic image, the toner set being composed of at least two kinds of cyan toners, The first cyan toner contains a silicon phthalocyanine compound having a structure represented by the following general formula (V), The second cyan toner contains a copper phthalocyanine compound. A toner set for developing electrostatic images, comprising: 【Chemistry 1】 [In the ceremony, Z 1 , Z 2 is a general formula (IV) in which R 1 , R 2 , and R 3 each are an alkyl group having 1 to 22 carbon atoms. 1 , Ra 2 , Ra 3 and Ra 4 each independently represents a substituent; na1, na2, na3, and na4 each independently represent an integer of 0 to 4. 【Chemistry 2】 [In the formula, R 1 , R 2 and R 3 each independently represent an alkyl group having 1 to 22 carbon atoms, an aryl group having 6 to 18 carbon atoms, an alkoxy group having 1 to 22 carbon atoms, or an aryloxy group having 6 to 18 carbon atoms. Note that R 1 , R 2 and R 3 may be the same group or different groups.]

2. 2. The toner set for developing an electrostatic image according to claim 1, wherein the difference in hue angle between the first cyan toner and the second cyan toner when the adhesion amount is 3.4 gsm is 10[deg.] or more.

3. 3. The toner set for developing electrostatic images according to claim 1, wherein the copper phthalocyanine compound has a neutral or basic substituent.

4. An electrophotographic image forming method having at least a step of charging an image carrier, a step of forming an electrostatic image, a step of developing the electrostatic image, a step of transferring a toner image, and a step of fixing the toner image, 4. An electrophotographic image forming method, comprising using the toner set for developing an electrostatic image according to claim 1.

5. An electrophotographic image forming apparatus comprising at least an image carrier charging means, an electrostatic image forming means, an electrostatic image developing means, a toner image transferring means, and a toner image fixing means, 4. An electrophotographic image forming apparatus, comprising the toner set for developing an electrostatic image according to claim 1.

Citation Information

Patent Citations

  • Toner

    JP2009093161A

  • Electrostatic charge image developing toner

    JP2009265227A

  • Cyan toner for electrostatic charge image development

    JP2014026066A

  • Full color image forming method

    WO2010007963A1